Hierarchical FeCoP nanosheets array anchored on phenolic resin derived N-doped porous carbon as a high-efficiency bifunctional electrocatalyst for alkaline water splitting - Qin Wang; Jiaxin Pei; Xiaoya Wei; Yangyang Li; Hongxin Li; Jiangyong He; Bi Chen; Jian Li; Yu Meng; Long Yan (Fuel, 2027)

Metabolomics-based analysis of dynamic metabolic trajectories and regulatory networks in two-stage fermentation of kiwifruit wine - Wangsheng Sun; Pengfei Bi; Wanju Yan; Rou Cai; Zhendong Zhang; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Jing Guo (Food Microbiology, 2027)

Impacts of high-altitude aerosol hygroscopicity on cloud microphysics in the North China Plain: A WRF fast-SBM modeling study - Qian Gao; Hui He; Xiang'e Liu; Yan Yang; Rong Yuan; Ping Tian; Kai Bi; Fei Wang; Jiujiang Sheng; Yongqing Wang (Atmospheric Research, 2026)

Constraints on Paleo-Pacific Plate rollback from magmatic spatiotemporal evolution, isotopic composition variations, and crustal thickness changes: Insights from Early Cretaceous adakitic granitoids in the northeastern Asian continental margin - Xinping Li; Yu Dong; Wenchun Ge; Simiao Wang; Junhui Bi; Hao Yang; Jie Tang; Hongying Zhou; Yan Jing; Guochun Zhao (Lithos, 2026)

Potassium ferrate combined with cation exchange resin achieved efficient protein extraction from primary sludge - Ling Wang; Huan Liu; Jinbiao Zhu; Yan Wang; Lei Gao; Xiaoqiu Lin; Xuejun Bi; Heliang Pang (Biomass and Bioenergy, 2026)

Effect of sugars and non-sugar sweeteners on aroma compound release, sensory quality and physical properties of flat peach puree and derived vacuum-freeze-dried products - Liya Liu; Lichang Yan; Yu Zhang; Jihong Wu; Xin Pan; Bo Cai; Shuang Bi; Ye Liu (Food Research International, 2026)

Management of blue mold development and quality maintenance on fresh Lanzhou lily during postharvest storage by micro-nano bubble ozone water - Zhaotong Duan; Zhenhang Lu; Tinghui Duan; Penghui Wei; Huali Xue; Yang Bi; Mei Li; Yan Yin (Postharvest Biology and Technology, 2026)

Characterization of GSTz2 involved in cyantraniliprole and emamectin benzoate detoxification in Drosophila suzukii - Yongqi Yan; Chongzhi Wang; Mingzhe Li; Shiwei Guo; Xuxing Li; Jingyan Yu; Xiaoqing Fang; Rui Bi (Journal of Asia-Pacific Entomology, 2026)

Tailoring polyhydroxybutyrate by molecular weight regulation: Green synthesis, food-grade performance and innovative ketogenic applications - Jin Hui Xie; Jia Ying Xin; Yan Wang; Li Rui Sun; Hai Xin Bi; Jian Xiong Zhang; Chun Gu Xia (Food Research International, 2026)

Facile fabrication of robust hydrophobic-oleophilic aerogel for oil/water separation and thermal management - Dongwei Bi; Shiyao Ma; Yitong Chen; Zhen Yang; Xiao Han; Yuedan Wang; Wenfu Yu; Yulong Zhang; Yueyang Hong; Jun Yan; Huimin Zhang (Environmental Research, 2026)

Boosting uranium adsorption performance by engineering flexible linkers in tannin-immobilized polyamide membranes - Hongru Zhang; Linping Yan; Zihe Li; Wei Luo; Xuepin Liao; Bi Shi (Desalination, 2026)

Azo-sulfonate functionalized collagen fibers for rapid and high-capacity uranium capture - Zihe Li; Linping Yan; Wei Luo; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2026)

Genome-wide linkage and association mapping identified a novel candidate gene, TaGLK-A1, underlying fructan content in wheat grain - Zhankui Zeng; Yue Zhao; Junge Bi; Qunxiang Yan; Wei Zhang; Feng Chen; Chunping Wang (Theoretical and Applied Genetics, 2026)
Key message A nuclear-localized G2-like transcription factor, TaGLK-A1 ( TraesCS7A02G539600 ), was identified as a strong candidate gene for grain fructan content in wheat using GWAS, linkage mapping and transcriptome analysis. Abstract Fructans, a type of natural polysaccharides or oligosaccharides polymerized from fructose molecules, play important physiological roles in crops and confer great health benefits to humans. In this study, we detected 78 stable loci associated with fructan content across all 21 wheat chromosomes across three environments and in the BLUE, explaining 4.4–10.0% of the phenotypic variance by a genome-wide association study (GWAS) using 243 wheat cultivars and advanced lines genotyped with the Axiom wheat 660 K single-nucleotide polymorphism (SNP) array. Among these, a significant locus of fructan content was localized in a 4.02 Mb interval (713.87–717.89 Mb) on chromosome 7AL, designated QGfc.hkd-7A . QGfc.hkd-7A was validated in 164 recombinant inbred lines (RILs) from a cross between Avocet and Chilero in five environments using diversity array technology (DArT), which was tightly linked to DArT markers SNP2260399 , 3575400 , SNP3028492 , SNP100415949 , 3533474 and 100091413 , accounting for 16.4–24.6% of the total phenotypic variance in the RIL population. Favorable allele of QGfc.hkd-7A significantly increased grain fructan content by 10.5% ( P QGfc.hkd-7A , we generated differential gene expression profiles using RNA-seq for high-fructan (AC6012) and low-fructan (AC6361) lines from the Avocet/Chilero population. TaGLK-A1 ( TraesCS7A02G539600 ), a differential expressed gene (DEG), was subsequently cloned and sequenced from both genotypes. Sequence comparison of the full-length TaGLK-A1 cDNA (1545 bp) revealed a single SNP at position 109 causing a proline (CCA) to threonine substitution between Avocet and Chilero. Subcellular localization analysis confirmed that the G2-like transcription factor encoded by TaGLK-A1 localizes to the nucleus. Transactivation assays revealed that it lacks intrinsic transcriptional activation activity, suggesting it may function as a transcriptional repressor or require cofactors for regulatory function. These results provide a novel and strong candidate gene for fructan content and a forward genetics strategy for gene discovery in molecular breeding.

Experimental Investigation on Damage Behavior of Soaked Sandstone under Multi-Stage Cyclic Loading - Zhenhui Bi; Yintong Guo; Wei Yan; Chunhe Yang; Laibin Zhang; Yuxiang Jing; Guangchao Wang (Rock Mechanics and Rock Engineering, 2026)

Machine learning–driven multi-objective optimization of electrospun nanofibrous membranes design for membrane distillation - Xiaolu Li; Kai Qi Yan; Xinxin Wei; Minjian Li; Jiawei Sun; Ying Bi; Lu Shao; Hanyu Gao; Alicia Kyoungjin An (Water Research, 2026)

Tectonic forcing and climate modulation on the evolution of aeolian sediment provenance from the northeastern Tibetan Plateau margin to the Chinese Loess Plateau - Yuxin Fan; Minmin Gao; Fei Wang; Qingsong Cai; Chuanying Zhu; Xueyu Yan; Ke Bi; Qiang Shu; Ping Zhang (Quaternary Science Reviews, 2026)

Halloysite surface-induced spin-state regulation and hydroxyl-assisted adsorption: A dual enhancement mechanism for PMS activation - Haiyi Lv; Sikai Zhao; Yan Li; Qiang Zhao; Xiaoyu Jiang; Hongshan Bi; Zhou Lin; Yanbai Shen (Chemical Engineering Journal, 2026)

Synergistic multi-site engineering of bound exciton relays for near-unity PLQY and stable NIR emission in lead-free perovskite inspired 0D metal halides - Aadil Ahmad Bhat; Wengang Bi; Yan Yang; Xiyuan Zhou; Tongtong Kou; Mohd Zeeshan; William W. Yu (Chemical Engineering Journal, 2026)

2-Methoxyestradiol Suppresses Stemness and Epithelial-Mesenchymal Transition in Drug-Resistant Esophageal Squamous Cell Carcinoma by Targeting the Snail Signaling Pathway in Cancer Stem Cells - Jie Yan; Shuhua Han; Keqi Zhang; Linlin Li; Mingjing He; Haoqing Cao; Meiru Zhu; Bingjie Bi; Qiang Xu; Cong Wang (Stem Cell Reviews and Reports, 2026)

Advances in carrier-free nanodrug delivery systems - Jin-Ye Liu; Yan-Yan Zheng; Shu-Yu Wang; Yan-Ping Bi; Ming-Shuang Sun; Ji-Fu Hao; Yu-Jing He (Drug Delivery and Translational Research, 2026)

FSCNet: a frequency–spatial collaborative enhanced image super-resolution network - Yubo Zhang; Juanjuan Geng; Wanying Zhao; Shaojuan Yan; Kaijia Cui; Junhao Bi; Chao Han; Yingjie Yuan (Computational Geosciences, 2026)

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

Seven previously undescribed seco-abietane and seco-isopimarane type diterpenoids from Biscogniauxia sp. and their biological activities - Meng Zhang; Yang Yan; Wen-Song Bi; Liu-Yang Ma; Dan Hu; Liang-Dong Guo; Zuo-Cheng Qiu; Guo-Dong Chen; Huan Zhao; Hao Gao (Phytochemistry, 2026)

Rhizosphere fungal communities and glomalin-related soil proteins underlie divergent drought responses in indica and japonica rice - Sihan ZHOU; Yanhan JI; Junguo BI; Jiaxuan XU; Jingrui QIU; Xiaoqin ZENG; Zixian JIA; Zijin BIAN; Ning LING; Shuai ZHAO; Sheng ZHOU; Lijun LUO; et al. (Pedosphere, 2026)

Source, transport and impact of biomass burning emissions in spring 2024 in Yunnan, China - Lihui Lv; Feng Xiang; Haitao Xie; Fei Qiu; Ying Pan; Zihuai Yi; Zenan Wang; Zhichao Liu; Limei Bi; Lu Zhao; Qianqian Sun; Shuai Wang; et al. (Journal of Environmental Sciences, 2026)

Evaluating Hangzhou’s urgent source-specific regulatory policies for the 2024 New Year haze: A receptor model and machine learning approach - Weizhao Liang; Yuan Li; Xuan Liu; Renchang Yan; Wubin Zhu; Yunshan Li; Jiandong Shen; Xiaohui Bi; Yufen Zhang; Qili Dai; Yinchang Feng (Journal of Environmental Sciences, 2026)

Quality-driven grinding control: Monitoring lipid oxidation markers for off-flavor mitigation in pea milk - Shuang Bi; Lichang Yan; Xiaoying Xiong; Fan Yang; Ye Liu (Food Control, 2026)

Invasions of alien plants pose unprecedented challenges to China’s nature reserves under climate change - Jia-Xin Wang; Rainer W. Bussmann; Fei Qin; Yun-Fen Liang; Bao-Cai Han; Hai-Yan Bi; Tian-Tian Xue; Sheng-Xiang Yu (Biodiversity and Conservation, 2026)

Zircon–monazite geochronology and zircon Hf–O isotopes of Ediacaran–Cambrian paragneiss from the Mashan Complex, Jiamusi Block, NE China: implications for sedimentary–metamorphic–tectonic evolution - Guan-Ying Yu; Hao Yang; Jia-Hao Jing; Zheng Ji; Yan-Long Zhang; Jun-Hui Bi; Wen-Chun Ge (International Geology Review, 2026)

Treatment of rare earth industrial wastewater by membrane distillation: Performance and membrane fouling characterizations - Yufan Bi; Yan Dang; Hongbin Wu; Haiyu Xu; Bin Qiu (Journal of Environmental Chemical Engineering, 2026)

Unveiling the key role of COF matrices in enhancing the OER performance of single-atom catalysis through electronic modulation - Zihan Wang; Chunyang Li; Ya Xu; Weiqiang Wei; Yanchao Bi; Yan He; Huifang Li (Chemical Engineering Journal, 2026)

Microenvironment responsive copper-polyphenol nanozyme hybrid hydrogel with NO/O2 release for healing diabetic infected wounds via immunomodulation and angiogenesis - Changyuan He; Ruiqi Liu; Siwei Bi; Li Zhang; Jun Gu; Bin Yan (Chemical Engineering Journal, 2026)

Forest development and seasonal variation drive functional reorganization of soil microbiomes and enzymatic activities - Ke Shi; Jiahui Liao; Manuel Delgado-Baquerizo; Xiaoming Zou; Han Y.H. Chen; Qing-fang Bi; Yu Fang; Zhengming Yan; Tingting Ren; Honghua Ruan (CATENA, 2026)

Phytochemical constituents of the branches and leaves of Callicarpa pedunculata R. Br. and their taxonomic distribution - Chenyu Guo; Yimiao Chen; Limin Chen; Feifei Bi; Xinying Zhang; Ruiying Liu; Keying Xu; Antao Luo; Dan Yan; Guijuan Zheng (Biochemical Systematics and Ecology, 2026)

TDP-43 Dysfunction Causes Hyper-Lactate State, Increased AARS1 Expression and Enhanced Protein Lactylation - Tianshuo Zhang; Kaixin Yan; Qiao Liao; Ruiyang Liu; Ruyuan Liu; Jinxia Zhou; Yongmin Liu; Fangfang Bi (Neurotoxicity Research, 2026)

Low abundance microorganisms enhance soil multifunctionality by emphasizing fungal roles as mediated by plant biomass - Ze-Ying Zhao; Xiao-Bin Xiong; Peng-Yang Wang; Jia-Cheng Guo; Yinglong Chen; Hong-Yan Tao; Nan Chang; Cheng-Rui Bi; Yun-Lu Chen; Yuan Song; You-Cai Xiong (Applied Soil Ecology, 2026)

Broadband Vibration Suppression of Spar-Type Offshore Wind Turbines Using a Novel Folded-Beam Nonlinear Energy Sink - Jinyu Li; Hui Liang; Yanliang Bi; Nana Sun; Yan Zhang; Hongyin Geng (Journal of Marine Science and Engineering, 2026)
Spar-type floating offshore wind turbines (FOWTs) operating in deep-sea environments are subjected to coupled wind and wave excitations spanning a wide frequency range, rendering single-frequency passive damping solutions inadequate. A folded-beam nonlinear energy sink (FB-NES) is proposed for broadband vibration suppression of spar-type FOWTs. The device employs pre-buckled elastic beam arms integrated with constrained layer damping patches, and a closed-form analytical relationship between the beam geometric parameters and the nonlinear stiffness coefficients is derived, enabling direct parameter design without iterative calibration. The pre-buckled geometry introduces a negative-stiffness mechanism that substantially lowers the targeted energy transfer (TET) threshold, ensuring device engagement under all normal operational sea states. A 14-degree-of-freedom aero-hydro-elastic model of the NREL 5 MW OC3-Hywind FOWT with the FB-NES is established via the Euler–Lagrange formulation and validated against OpenFAST. Based on the numerical results under operational and extreme parked load cases, the FB-NES achieves substantial broadband vibration reductions that grow monotonically with wave severity, consistently and substantially surpassing both the optimally tuned mass damper (TMD) and a conventional cubic nonlinear energy sink of equal mass. Wavelet analysis confirms that targeted energy transfer, rather than direct viscous damping, is the dominant energy dissipation mechanism. The FB-NES also maintains effective control over a wide frequency detuning range, demonstrating superior robustness compared to the TMD.

Experimental investigation on the dynamic response of approach bridge and wharf structures under vessel collision - Yan Zhu; Cuizhu Zhao; Ming Peng; Qingxin Zhao; Jingchao Bi; Yu Huang (Ocean Engineering, 2026)

Ship hydrodynamic optimization for minimum resistance through an improved grey wolf algorithm and ship model experimental verification - Jie Liu; Li-fen Hu; Bao-ji Zhang; Yong-yi Jiang; Jun-ying Bi; Ying-kai Dong; Guo-hua Yan (Ocean Engineering, 2026)

High-resolution point source pollution database boosts SWAT-QUAL2K coupled model for multi-scale nitrogen and phosphorus management - Yang Bi; Yanxin Zhao; Yi Rong; Ningtong Li; Kai Huang; Yan Chen (Journal of Cleaner Production, 2026)

Synergistic electrocatalytic-biological degradation of Ni-EDTA in a baffled three-dimensional reactor: Performance optimization and mechanism analysis - Huihui Sheng; Yan Feng; Xinqiang Jia; Xinwei Wang; Yuyu Lu; Jingran Bi; Yanzhen Yu (Journal of Cleaner Production, 2026)

Distinct amino acid synthesis constraints regulate aroma ester formation under carbon–nitrogen adjustment in Cyberlindnera fabianii - Chuntong Ma; Shupei Sun; Ying Liu; Yingying Bi; Lijie Zhang; Yan Xu; Yao Nie (Systems Microbiology and Biomanufacturing, 2026)

Organic fertilization alleviates soil sickness in monoculture systems by driving pathogen-suppressive rhizosphere community assembly - Tong Peng; Chuanji Zhang; Xiaoqi He; Zhenyu Cheng; Junjie Li; Yanfang Song; Ziyu Liu; Meiyun Pu; Yi Yan; Panshuai Fei; Yurong Bi; Xiaofan Na (Plant and Soil, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

Structural vibration analysis and safety assessment of centrifuges under hypergravity environments - Chengpeng Hong; Guanwen Liang; Li Bi; Haoran Fu; Zizhuang Yan; Kuigen Lin; Yunmin Chen (Engineering Structures, 2026)

Occurrence, Distribution and Ecological Risk Assessment of Phthalate Esters in Sediments of Poyang Lake and its Tributaries - Yan Ma; Runxuan Li; Qingyuan Liu; Ke Zhang; Jiale Bi; Bo-Tao Zhang; Yan Liu; Peng Shao (Water, Air, & Soil Pollution, 2026)

Subcellular Structures in Native Hippocampal Synapses Revealed by Cryo-electron Tomography - Chong-Li Tian; Lei Qi; Zhen-Hang Lu; Shuo Liu; Min-Ling Gu; Wen-Lan Huang; Yi-Tong Yan; Yun-Tao Liu; Jing Wu; Peiyi Wang; Z. Hong Zhou; Guo-Qiang Bi; et al. (Neuroscience Bulletin, 2026)

Isolation and identification of a centromeric tandemly repeated DNA sequence in Saccharina japonica - Yi-Yan Cai; Cheng Zhang; Si-Qi Chen; Zhi Li; Zhi-Gang Zhou; Yan-Hui Bi (Algal Research, 2026)

Ginkgolide B-cyclodextrin inclusion complexes: an encapsulation strategy for improved solubility and aerosol inhalation therapy in bronchial asthma - Yuying Wang; MingLi Wei; Yan Zhang; Yuxin Liu; Xiaoshuang Bi; Xingting Fan; Jingxin Gou; Haibing He; Xing Tang; Yu Zhang; Tian Yin (Drug Delivery and Translational Research, 2026)

Three new matrine-type alkaloids from Sophora alopecuroides with cytotoxic activity - Yan-Ping Qiu; He Tian; Qian Xie; Shuai Li; Bi-Qian Dong; Guan-Min Su; Ding Luo; Lin-Zhao Ye (Phytochemistry Letters, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

Effect of S, N co-doped carbon-based supports on low-temperature NH3-SCR: Resistance to SO2, H2O and denitrification mechanism - Shuangshuang Yan; Dongmei Bi; Shiyan Sun; Hui Wang; Xiang Zhu; Long Wang; Shanjian Liu (Journal of Environmental Chemical Engineering, 2026)

Effects of metals on thermal oxidation of jet fuel and mitigation strategies - Bowang Lu; Xiaoyong Fan; Dong Li; Jun Yang; Long Yan; Bo Yang; Guanghui Pang; Jian Li; Bi Chen (Fuel, 2026)

Corrigendum to “Genomic and functional characterization of the lect2 gene from Siniperca chuatsi” [Fish Shellfish Immunology 107 (2020) 146–155] - Yawei Shen; Ming Cao; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen; Yanhui Bi (Fish & Shellfish Immunology, 2026)

A customizable three-dimensional-printed triaxial force sensing finger cot with residual fully connected neural network algorithm for wearable hand rehabilitation - Yang Chen; Jinglong Bi; Yue Hu; Yang Gao; Xijin Hua; Yabin Yan; Tianyao Jia; Fuzhen Xuan (Chemical Engineering Journal, 2026)

Sustainable 3D graphene foam for electromagnetic interference shielding via tandem waste reforming and chemical vapor deposition - Huiyang Bi; Mingyue Yan; Zhichun Huang; Chen Sun; Zhongjian Li; Yang Hou; Lecheng Lei; Bin Yang (Chemical Engineering Journal, 2026)

Seismic performance of beam-column joints reinforced with ECC - Long Liu; Hongbo Xiao; Songqiang Wan; Chunling Yan; Yu Wang; Chong Liu; Xiaoze Yang; Liang Cui; Chenjie Hao; Menghao Ming; Boyang Liu; Yingying Bi (Bulletin of Earthquake Engineering, 2026)

Modeling and analysis of electromagnetic, fluid and energy characteristics in flat linear induction pump - Sixian Zhu; Jien Ma; Zheng Wang; Keming Bi; Xin Yan; Youtong Fang (Annals of Nuclear Energy, 2026)

Numerical study on three-dimensional coupling characteristics for electromagnetism and flow in flat linear induction pump - Heyao Li; Zhuqian Zhang; Lixin Yang; Keming Bi; Xin Yan; Haojie Zhang; Xiao Chen (Annals of Nuclear Energy, 2026)

Brachymonas moutaii sp. nov., a floc-forming bacterium isolated from a distillery wastewater treatment plant - Yaqi Liu; Hui Wang; Ansi Jiang; Junmei Wu; Bi Chen; Yong Zhang; Siliang Yuan; Yan Huang; Haiyan Zeng; Xin Wang; Dian Jiao; Wei Li; et al. (Antonie van Leeuwenhoek, 2026)

United-modality underwater object tracking via distinct enhancing and high-dimensional fusion - Kaixiang Yan; Wenhua Qian; Cong Bi; Jie Liu (Ocean Engineering, 2026)

Pore-scale numerical modeling of transport kinetics for CCUS-EOR and carbon cycling in offshore–onshore integrated energy system - Lufei Bi; Jing Li; Yiqi Zhang; Lijun Min; Renfeng Yan; Lijun Zhan; Nan Yang; Shenglai Yang; Zhangxing Chen (Fuel, 2026)

Analysis of the effects of amino acids and polyphenols on the bitterness of salt reduced soy sauce - Xingming Sun; Yongzhao Bi; Yan Huang; Qiuyu Zhu; Baoguo Sun; Lili Zhang; Dong Liang; Yuyu Zhang (Food Chemistry, 2026)

Modulating excited states of multiple resonance emitter via through-space conjugation toward pure-green electroluminescence - Xiaoxian Song; Junxuan Lin; Zhiqiang Li; Zhiping Yan; Xuming Zhuang; Hai Bi; Yue Wang (Chemical Engineering Journal, 2026)

Beyond adsorption: Supramolecular bio-gel triggers heavy-metal contaminated soil's self-remediation via electron-cage catalyzed lattice sealing - Gaoyuan Gu; Yan Zhou; Jianing Zhang; Xinyao Wang; Chong Peng; Yuanfei Wang; Changlong Bi; Shuyi Yang; Tao E (Chemical Engineering Journal, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Ecological risk assessment of organochlorine pesticides in coastal sediments: A multi-level approach in the greater bay area - Jie Wang; Guiming Bi; Yingdong Tang; Yun Shao; Chao Wei; Lei Zheng; Yizhe Wang; Zhenguang Yan (Regional Studies in Marine Science, 2025)

Two new compounds from the roots of Mirabilis jalapa L. and their cytotoxic activity in vitro - Xiao-Mei Yan; Tian-Tian Qu; Jie Luan; Hou-Run Zhang; Xiang-Qin Tang; Xiao-Xu Bi; Ying Wang; Bing Chen; Jiang-Bo He (Phytochemistry Letters, 2025)

Thickened active layer contribute less to vegetation growth over the Tibetan Plateau - Wenwen Li; Denghua Yan; Baisha Weng; Yuequn Lai; Wuxia Bi; Lin Zhu; Zhaoyu Dong; Yuhang Zhang; Jianyun Zhang; Hao Wang (Journal of Hydrology, 2025)

Physics-constrained interpolation synergizes with machine learning for diethyl phthalate removal mechanism in water under sparse data - Dongmei Bi; Hui Wang; Shuangshuang Yan; Chengxizi Zhang; Jiawen Zhang; Shanjian Liu; Weiming Yi (Journal of Environmental Chemical Engineering, 2025)

Decoding bitter peptides in soy sauce: From identification to mechanism in bitter taste formation - Yongzhao Bi; Xingming Sun; Yan Huang; Baoguo Sun; Li Liang; Yuyu Zhang (Food Chemistry, 2025)

Toxicokinetics of typical halogenated organic pollutants (HOPs) in frogs (Rana tigrina cantor) via skin exposure and effects of hibernation - Ke-Lan Guan; Xiao-Jun Luo; Chu-Hong Zhu; Jian Guo; Yan-Hong Zeng; Bi-Xian Mai (Environmental Pollution, 2025)

Conjugated imine phenolic resins with high strength, superior toughness, and rapid curing at low temperatures - Ruohong Bian; Pu Liu; Zhanlong Bi; Zhiqin Wang; Ximing Yuan; Yan Lyu; Yuhan Liu; Kaiqi Wang; Xiaona Li; Jianzhang Li; Jiongjiong Li (Chemical Engineering Journal, 2025)

Effect of transgene on salt tolerance of tobacco - Jie Sun; Yan Dong; Yuemei Meng; Jingran Bi; Hongmei Liu; Junjie Ren; Jinmao Wang; Yachao Ren; Minsheng Yang (Transgenic Research, 2025)

Intercellular crosstalk within human preimplantation lineages regulates trophectoderm specification - Zhifen Tu; Yan Bi; Tan Lin; Tao Wu; Hong Wang; Jingyu Li; Guoning Huang; Shaorong Gao; Yixuan Wang (Science Bulletin, 2025)

Warm-dry climate narrowed the difference between vegetation greenness and photosynthetic phenology periods in the Yellow River Basin, China - Yan Liu; Jialin Bi; Xiaoyu Cai; Liping Wang; Guoqing Li; Xiaohui Wang; Xianbin Liu; Zhanpeng Xu; Xiang Yu; Chao Zhan (Remote Sensing Applications: Society and Environment, 2025)

Sesamol inhibits fungal growth by destroying the redox dynamic equilibrium in Pestalotiopsis neglecta - Jing-Yu Ji; Li-Ying Huang; Bing Bi; Ya-Jun Wang; Jin-Yan Zhao; Sheng-Yu Zhang; Ze Wang; Shu-ming Cui; Qiao-ya Zhang; Guo-Cai Zhang (Physiological and Molecular Plant Pathology, 2025)

Soil moisture measurement and supplementary irrigation to enhance strong-gluten wheat processing quality via altering GMP particle size distribution - Jingxin Bi; Haoyu Li; Min Yang; Yuxian Jiang; Yajiao Wang; Yanfei Yan; Yaokuo Wang; Ruiguo Cai; Min Zhang (Journal of Cereal Science, 2025)

Absorptive and transport roots of two tree species respond differently to soil salinity along soil depth - Yan Wang; Xiaohui Guo; Qiulin Bi; Wen Zhou; Hongxi Yao; Jiacun Gu; Yanping Wang (Flora, 2025)

Species- and sex-specific bioaccumulation, tissue-specific distribution, and maternal transfer of per- and polyfluoroalkyl substances in tiger frogs (Hoplobatrachus chinensis) and forest frogs (Rana chensinensis) - Chu-Hong Zhu; Xiao-Jun Luo; Xi Chen; Peng-Peng Chen; Ke Lan Guan; Yan-Hong Zeng; Bi-Xian Mai (Environmental Research, 2025)

3D printed electrochemical sensors with femtosecond laser treatment for cellphone-based portable detection - Yan Dou; Kewei Li; Haofan Sun; Kun Bi; Chenyang Zhu; Zuanyu Chen; Kailong Jin; Wonmo Kang; Xin Zhao; Qiong Nian (Chemical Engineering Journal, 2025)

Engineering metal ion-coordinated DNA nanospheres for precise detection of specific chemoresistance-dependent signaling pathway and reversion in live cancer cells - Shunmei Li; Xin Bi; Huaifeng Yan; Bingying Jiang; Ruo Yuan; Yun Xiang (Chemical Engineering Journal, 2025)

Metabolic Control of Stem Cell Function: Insights into Amino Acid-Driven Mechanisms - Jiawei Zeng; Xiaohao Liu; Jiaming Bi; Chuzi Mo; Han Zhang; Yan Chai; Yunhe Lin; Siwei Li; Zhongjun Liu; Mingyan Yao; Shuaimei Xu; Peiyan Yuan (Stem Cell Reviews and Reports, 2025)

Predictors of mortality and progression from colonization to Stenotrophomonas maltophilia bloodstream infection in hematologic disorders: a single-center retrospective study - Hongchen Bi; Qingsong Lin; Qi Sun; Yanxia Lv; Zhiying Tian; Xue Fu; Qiushuang Yan; Yaqing Yu; Hongjing Yao; Fujun Sun; Yonghui Xia; Aiming Pang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Experimental study and generalized predictive model of thermal conductivity of saline soil - Zhongrui Yan; Zhiliang Liu; Xusheng Wan; Jun Bi; Jun Diao; Yongqiang Cao (Bulletin of Engineering Geology and the Environment, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Biotransformation causes the sex-specific regulation of polychlorinated biphenyls during metamorphosis of silkworm (Bombyx mori) and their effect on the silkworm development - Xue-Meng Qi; Xiao-Jun Luo; Pei-Xin Su; Peng-Peng Chen; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Integrating HS-SPME-GCMS with chemometrics for identifying adulterated flaxseed oils and tracing origins of additives - Yan-Jin Wen; Long-He Wang; Meng Zhai; Hui Ma; Hua-Peng Cui; Lu Han; Guo-Bi Chai; Yi Lv; Qing-Xia Zheng; Yong-Jie Yu; Yuan-bin She (Food Control, 2025)

Effects of hibernation on the bioaccumulation and tissue distribution of per- and polyfluoroalkyl substances in frogs (Rana tigrina cantor) via skin exposure - Chu-Hong Zhu; Xiao-Jun Luo; Ke-Lan Guan; Jian Guo; Peng-Peng Chen; Xi Chen; Yan-Hong Zeng; Bi-Xian Mai (Environmental Pollution, 2025)

Integrated carbon sequestration and agricultural efficiency enhancement: Reconstruction of tomato ecosystem carbon cycle via carbonized biomass ash-biogas slurry system - Feihong Liang; Xianwen Meng; Taifei Bi; Zhan Shi; Andrea Pezzuolo; Te Tu; Shuiping Yan; Qi Feng (Chemical Engineering Journal, 2025)

Microbially induced phosphate precipitation disentangles sludge retention time trade-off enabling efficient phosphorus removal with minimal sludge discharge in aerobic granular sludge - Peng Bi; Xiaohui Yan; Yueying Song; Hebin Miao; Hui Sun; Ying Han; Long Chen; Kangxin Yan; Mingyang Li; Fan Xiong; Jingwei Ma; Qiulai He (Chemical Engineering Journal, 2025)

An antioxidative sodium alginate hybrid hydrogel with NIR-controlled NO releasing for diabetic wound healing via reduced inflammation and enhanced angiogenesis - Changyuan He; Siwei Bi; Li Zhang; Jun Gu; Bin Yan (Carbohydrate Polymers, 2025)

Emerging role of RNA m6A modifications in laryngeal squamous cell carcinoma: insights into tumorigenesis and therapeutic potential - Guotong Zheng; Jing Bi; Yangyan Yan; Bo Yu; Yong Fu (Apoptosis, 2025)

Seasonal Variations and Potential Sources of Black Carbon at a Mountain Site in the Central Yunnan Plateau, China - Yanli Wang; Yan Cheng; Song Liu; Feng Xiang; Limei Bi; Qiaoli Wu; Xuan Tian; Shiting Chen; Zechen Gu; Feng Wu (Aerosol Science and Engineering, 2025)

Rupture mechanism of a liquefied gas storage tank in fire and occurrence prediction of a BLEVE - Weiye Luo; Xingtao Dai; Jingjie Ren; Bing Han; Yan Liu; Jun Hu; Mingshu Bi (Process Safety and Environmental Protection, 2025)

Phthalocyanine-based nanosensitizers for enhanced sonodynamic therapy activity of hypoxic tumor with dual apoptosis/ferroptosis pathways - Xue-Yan Li; Jin Liu; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Edge nucleation and bridging effect synergistically in-situ sealed multiple heavy metals in soils - Gu Gaoyuan; Zhang Jianing; Zhou Yan; Ge Ruijie; Li Wenhui; Peng Chong; Wang Yuanfei; Bi Changlong; Yang Shuyi; E Tao (Journal of Hazardous Materials, 2025)

A generative ozone concentration imputation and forecasting method based on a novel conditional diffusion model - Liangliang Mu; Suhuan Bi; Kai Yan; Xiangqian Ding; Yan Xu (Journal of Hazardous Materials, 2025)

Research on the effects of split injection on diesel engine spray impingement and fuel film under cold-start conditions - Jie Yan; Luxin Fu; Weizheng Zhang; Xu He; Shuang Jin; Zhenyao Guo; Huahong Yu; Sinan Bi (Fuel, 2025)

Elimination of mycotoxins in dried apricots: The role of nitric oxide in suppressing production and facilitating degradation mechanisms - Yan Chen; Shunxin Bi; Chuanxing Wang; Jian Zhang; Die Chen; Shangcheng Ying; Chen Chen; Wenxuan Lei; Yadong Zhao; Bin Wu; Jide Wang (Food Chemistry, 2025)

Effect of non-Saccharomyces yeast combinations and lactic acid bacteria inoculation timing on fermentation performance and aroma quality of kiwifruit wine - Wangsheng Sun; Wanju Yan; Rou Cai; Zhendong Zhang; Pengfei Bi; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Fangyu Long; Jing Guo (Food Bioscience, 2025)

Calcium-modified siderite-driven optimization of sulfur autotrophic denitrification systems: Synergistic nitrogen/phosphorus removal and multidimensional mechanism insights - Can Yang; Yan Wang; Junyu Xuan; Jinquan Wan; Zhangqing Bi (Bioresource Technology, 2025)

Effects of Land-Use Change on Soil Infiltrability and Preferential Flow in Typical Low Hilly Area - Linlin Chu; Rong Ma; Yue Liu; Yan Zhao; Lidong Bi; Chen Dan (Journal of Soil Science and Plant Nutrition, 2025)

Modeling and optimization of planar induction electromagnetic pump based on genetic algorithm mixed with parameter sweep - Wenxiao Wu; Jien Ma; Keming Bi; Xin Yan; Youtong Fang (Annals of Nuclear Energy, 2025)

A new triterpenoid saponin and a new natural saponin from the roots of Bupleurum scorzonerifolium willd - Zi-Wei Li; Jia-Tong Wu; Yu Bi; Meng-Meng Li; Anam Naseem; Juan Pan; Wei Guan; Zhi-Chao Hao; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Yan Liu; et al. (Natural Product Research, 2025)

The impact of enclosure management on the conservation and restoration of microbial community in a typical urban lake - Hanhui Huang; Kangxin Xiao; Tianqiao Shen; Dongliang Chu; Zhicai Xie; Yonghong Bi; Kang Ning; Yunjun Yan (Science of The Total Environment, 2025)

Prediction of shear characteristics at core pile-cemented soil interface for offshore wind turbine pile foundation based on machine learning - Yu-liang Yan; Yu-xi Zeng; Yong-chao Liu; Bing-bing Li; Xiu-feng Liu; Bi-sheng Xu (Ocean Engineering, 2025)

Evaluation of ensiled protein grass as a novel feed ingredient in diets for lambs: Effects on fattening performance, meat quality and flavor - Yanmei Zhang; Chunxu Yang; Bo Chen; Wei Zhou; Naifeng Zhang; Yan Tu; Qiyu Diao; Tao Ma; Huaisen Chen; Kai Chen; Mahmoud M. Abdelsattar; Yanliang Bi (Food Chemistry, 2025)

Efficient dual broadband VIS-NIR emission in Mo-doped double perovskites enabling detection and imaging applications - Xin Li; Jinming Yan; Liang Wang; Lanbo Shen; Feng Jiang; Fujun Zhang; Jiayi Xu; Qilin Wei; Tong Chang; Zilong Wu; Terefe Tafese Bezuneh; Xue Bai; et al. (Chemical Engineering Journal, 2025)

Aluminum ion-activated low-temp pyrolyzed carbon to decontaminate Cr in water and soil - Jianing Zhang; Gaoyuan Gu; Shuyi Yang; Yan Zhou; Jianhua Li; Chong Peng; Yuanfei Wang; Yun Li; Changlong Bi; Tao E (Science of The Total Environment, 2025)

Associations of non-essential metal mixture with biological aging and the mediating role of inflammation in Chinese older adults - Yan Zhang; Yuan Wang; Xuqiu Cheng; Ziwei Tian; Yuantao Zhang; Wenyuan Liu; Xianglong Liu; Bing Hu; Fangbiao Tao; Anna Bi; Jun Wang; Linsheng Yang (Environmental Pollution, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Co-pyrolysis of polyurethane and biomass: Piperidine derivative production and nitrogen mechanism modulation by flame retardants - Yu Ni; Dongmei Bi; Shuangshuang Yan; Hui Wang; Chunwang Dong; Shanjian Liu (Chemical Engineering Journal, 2025)

Eutrophication‐induced dinoflagellate succession contributes to marine carbon sequestration through refractory dissolved organic matter accumulation - Fu‐Tao Fang; Zhuo‐Yi Zhu; Yuan‐Bi Yi; Ding He; Hong‐Yan Bao; En‐Ren Zhang; Cheng‐Xu Zhou (Limnology and Oceanography, 2025)
The increasing eutrophication of coastal seas is causing a shift in the most important phytoplankton groups from diatoms to dinoflagellates, but its feedback to marine carbon cycling remains unclear. Here, we investigated the potential of the key coastal phytoplankton, the diatom Skeletonema costatum , and the dinoflagellate Prorocentrum donghaiense , for refractory dissolved organic carbon (DOC) accumulation over dark degradation incubations of 70 d. Our multi‐method approach showed that dinoflagellate detritus, rather than diatom detritus, significantly contributes to refractory DOC. This is evidenced by the fact that the detritus of dinoflagellates compared to that of diatoms (1) has a weaker transmittance in infrared spectrometry, indicating a lower content of labile organic substances (alcohol and amide groups); (2) has a higher release and/or transformation efficiency of particulate organic carbon to DOC (81% vs. 50%); (3) has a lower content of labile fraction, amino acid (8% vs. 17% carbon) and exhibits lower degradability of the DOC formed (23% vs. 30%); (4) has a lower content of labile compounds determined by Fourier transform ion cyclotron resonance mass spectrometry (maximum molecular lability boundary: 21% vs. 31%); and (5) has a higher proportion of refractory carboxylic‐rich alicyclic molecules (57% ± 0.5% vs. 51% ± 0.7%) over incubations. Our results emphasize that eutrophication‐triggered coastal dinoflagellate succession has a significant potential for positive feedback to carbon sequestration through the formation of refractory DOC.

Inhibitory effect and mechanism of lipopeptide Iturin A on food spoilage yeasts - Zhemin Li; Wencheng Jiao; Xiufang Bi; Xinyao Xie; Dan Shu; Di Luo; Jie Yang; Zhiying Yan; Hong Tan (Food Bioscience, 2025)

Physiological responses and metabolic mechanisms of marine Chlorella under hypotonic stress: Implications for nutrient removal and starch accumulation - Zhangqing Bi; Jinquan Wan; Changzheng Wu; Yan Wang (Environmental Research, 2025)

Study on the degradation characteristics and strength prediction model of sandstone joints under wetting and drying cycles - Liu He; Jiaxin Yan; Junxiang Bi; Zihai Peng; Liwei Bai (Bulletin of Engineering Geology and the Environment, 2025)

Nitrogen/oxygen-codoped carbon aerogel electrode for excellent deammoniation performance using a flow-electrode capacitive deionization - Qilin Liu; Yan Lei; Xingtao Xu; Songhu Bi; Xiuchan Xiao (Desalination, 2025)

Inhibition of KDM6B prevents osteoarthritis by blocking growth plate-like H3K27me3 loss in bivalent genes - Hao Du; Yao Zhang; Xi Yu; Xuanhe You; Diwei Wu; Ze Du; Yongrui Cai; Zhenyu Luo; Hanpeng Lu; Zhixin Liao; Bi-Sen Ding; Ya Zhao; et al. (Science China Life Sciences, 2025)

Role of benzothiadiazole in regulating reactive oxygen species and inhibiting cap opening in Agaricus bisporus during storage - Ruirui Yang; Yanan Wei; Hui Peng; Ting Wang; Jianmin Yun; Yan Yin; Yang Bi (Postharvest Biology and Technology, 2025)

Sensing H2O2 for defense in plants - Yan Bi; Leeza Tariq; Hui Wang; Fengming Song (Molecular Plant, 2025)

A novel light-responsive sandwich-like nanocomposite film with efficient antibacterial activity for chilled beef preservation - Yirui Zhao; Hongshun Hao; Gongliang Zhang; Jingran Bi; Shuang Yan; Feng Hong; Hongman Hou (Food Bioscience, 2025)

Comprehensive upcycling waste siloxane liquid into H2-enriched syngas and silicon carbide via a tandem thermochemical process - Huiyang Bi; Bo Wu; Mingyue Yan; Chen Sun; Zhongjian Li; Yang Hou; Lecheng Lei; Bin Yang (Chemical Engineering Journal, 2025)

Synergistic effect Boosting the decomposition of hydrazine nitrate on bimetallic Pt-Ru alloy catalysts - Binglian Liang; Wenjie Yan; Guiyue Bi; Hai Shi; Yaqi Yao; Xu Zhang; Guoliang Xu; Yang Su; Kaixin Zhu; Xiaofeng Yang; Xuqun Zhao; Yanqiang Huang (Chemical Engineering Journal, 2025)

hUC-MSCs Prevent Acute High-Altitude Injury through Apoe/Pdgf-b/p-Erk1/2 Axis in Mice - Siyu Yan; Youkun Bi; Qun Liu; Shaole Song; Lihong Ma; Guangju Ji (Stem Cell Reviews and Reports, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Microbial biomass stoichiometry and proportion of Fe organic complexes separately shape the heterogeneity of mixotrophic denitrification and net N2O sinks in iron-carbon amended ecological ditch - Bi-Ni Jiang; Ying-Ying Zhang; Yan Wang; Hai-qin Liu; Zhi-Yong Zhang; Yi-Jing Yang; Hai-Liang Song (Water Research, 2025)

Source-specific soil heavy metal risk assessment in arsenic waste mine site of Yunnan: Integrating environmental and biological factors - Weigang Huang; Yanwei Liu; Xiaoyang Bi; Yan Wang; Huashou Li; Junhao Qin; Jingjing Chen; Zhepu Ruan; Guikui Chen; Rongliang Qiu (Journal of Hazardous Materials, 2025)

Accumulation of lipophilic and proteinophilic halogenated organic pollutants (HOPs) in the different types of feathers of laying hens - Xi Chen; Xiao-Jun Luo; Qun-Jie Feng; Yu Liu; Jun-Zhe Dai; Peng-Peng Chen; Pei-Xin Su; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Variations in Iron-bound carbon in Scirpus mariqueter rhizosphere and bulk soils across different salinities and tidal elevations - Yuxin Bi; Tianyou Li; Wenzhen Zhao; Liming Xue; Ying Lei; Qiqiong Zhang; Xiaoqing Gao; Xiuzhen Li; Zhongzheng Yan (Plant and Soil, 2025)

Single-Neuron Reconstruction of the Macaque Primary Motor Cortex Reveals the Diversity of Neuronal Morphology - Siyu Li; Yan Shen; Yefei Chen; Zexuan Hong; Lewei Zhang; Lufeng Ding; Chao-Yu Yang; Xiaoyang Qi; Quqing Shen; Yanyang Xiao; Pak-Ming Lau; Zhonghua Lu; et al. (Neuroscience Bulletin, 2025)

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

Synthesis and antibacterial activity of environmentally friendly sulfonium compounds - Jing Li; Wenyang Chen; Xinrui Bi; Yue Lin; Chengcai Liu; Yan Sun; Guinan Shen (Medicinal Chemistry Research, 2025)

Hyperconnectivity and Connectome Gradient Dysfunction of Cerebello-Thalamo-Cortical Circuitry in Alzheimer’s Disease Spectrum Disorders - Chenyang Yao; Yi Shan; Bixiao Cui; Zhigeng Chen; Sheng Bi; Tao Wang; Shaozhen Yan; Jie Lu (The Cerebellum, 2025)

Aluminum ion catalyzed proton transfer: Mechanism on promoting highly stable passivation of Cr by soil organic matter - Gaoyuan Gu; Jianing Zhang; Yan Zhou; Wenhui Li; Chong Peng; Changlong Bi; Shuyi Yang; Yun Li; E. Tao (Science of The Total Environment, 2025)

Provenance of fine-grained Quaternary sediments in the Tengger Sandy Desert recorded by Sr-Nd isotopes and its linkage with Quaternary aeolian silts on the Chinese Loess Plateau - Yuxin Fan; Minmin Gao; Fei Wang; Qingsong Cai; Guangliang Yang; Chunlei Zong; Ke Bi; Xueyu Yan; Qiang Shu; Bowen Kong (Quaternary Science Reviews, 2025)

Corrigendum to “Mesozoic–Cenozoic exhumation of the giant Jinchuan Ni-Cu sulfide deposit, China: Evidence from single-grain apatite (U-Th)/He ages” [J. Asian Earth Sci. 271 (2024) 106231] - Qingsong Cai; Xueyu Yan; Yuxin Fan; Minmin Gao; Guangliang Yang; Ke Bi; Ying Wang; Chuanying Zhu; Mingjie Zhang; Xiaohu Li (Journal of Asian Earth Sciences, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

The characteristics of phthalate acid esters and bisphenol A in PM2.5 of a petrochemical city: Concentrations, compositions, and health risk assessment in Dongying - Fangyun Long; Yanqin Ren; Yuanyuan Ji; Xurong Bai; Hong Li; Gehui Wang; Xiaoyu Yan; Yubao Chen; Junling Li; Haijie Zhang; Rui Gao; Fang Bi; et al. (Environmental Pollution, 2025)

Inorganic-rich solid electrolyte interphase and oriented (002) crystal plane extension for reversible zinc metal anode - Biyao Du; Jingzhu Chen; Yang Xu; Zhuoran Lv; Peng Ying; Wujie Dong; Luke Yan; Hui Bi; Fuqiang Huang (Chemical Engineering Journal, 2025)

End-to-end residual learning embedded ACWGAN for AHU FDD with limited fault data - Jian Bi; Ke Yan; Yang Du (Building and Environment, 2025)

IsoVISoR: Towards 3D Mesoscale Brain Mapping of Large Mammals at Isotropic Sub-micron Resolution - Chao-Yu Yang; Yan Shen; Xiaoyang Qi; Lufeng Ding; Yanyang Xiao; Qingyuan Zhu; Hao Wang; Cheng Xu; Pak-Ming Lau; Pengcheng Zhou; Fang Xu; Guo-Qiang Bi (Neuroscience Bulletin, 2025)

A novel hybrid model for annular linear induction pump - Sixian Zhu; Jien Ma; Keming Bi; Xin Yan; Youtong Fang (Annals of Nuclear Energy, 2025)

Interface-controlled synthesis of nickel phyllosilicate for efficient CO2 hydrogenation to methane: Breaking limitation of the conventional silica-surface-controlled synthesis - Wenhui Bi; Tengfei Zhang; Qing Liu; Yan He; Peng Liang (Fuel, 2025)

Radiofrequency affects the decrystallization efficiency and physicochemical properties of rape honey via crystal structure modification and inactivating enzyme - Shi-Ye Luo; Jia-Li Tao; Yan-Xiang Bi; Hong-Wei Xiao; Hua-Lei Chen; Xiang-Xin Li; Yin-Chen Wang; Xiao-Ming Fang (Food Chemistry, 2025)

Exposure to multiple metals and leukocyte telomere length in children and adolescents: The mediating effect of thyroid hormones - Qing Liu; Gaojie Fan; Jianing Bi; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Binghai Liu; Lianyan Yan; Wenwen Guo; Liqin Hu; Surong Mei; et al. (Environmental Research, 2025)

Remelting of the Songpan-Ganze slab: Contribution to elevated magmatic oxygen fugacity and reactivation of copper in the Yulong porphyry copper deposits belt - Yue Xu; Quanshu Yan; Leiluo Xu; Kun Guo; Xianwu Bi (Chemical Geology, 2025)

Semi-supervised CWGAN-GP modeling for AHU AFDD with high-quality synthetic data filtering mechanism - Hua Wang; Jian Bi; Mei Hua; Ke Yan; Afshin Afshari (Building and Environment, 2025)

Three-dimensional Fluorescence Spectrum Characteristics and Source Analysis of Dissolved Organic Matter in Sewage Outfall into the Sea of Dongguan - Changzheng Wu; Jinquan Wan; Jinpeng Wang; Jinlan Cai; Xiuwen Ren; Yan Wang; Zhangqing Bi (Water, Air, & Soil Pollution, 2025)

Establishment of Biopredictive Dissolution and Bioequivalence Safe Space Using the Physiologically Based Biopharmaceutics Modeling for Tacrolimus Extended-Release Capsules - Fulin Bi; Tong Yuan; Baohong Zhang; Jixia Li; Yan Lin; Jin Yang (AAPS PharmSciTech, 2024)

Effects of salinity on iron-organic carbon binding in the rhizosphere of Kandelia obovata: Insights from root exudate analysis - Ying Lei; Yuxin Bi; Xinhan Dong; Hongcheng Li; Xiaoqing Gao; Xiuzhen Li; Zhongzheng Yan (Science of The Total Environment, 2024)

Cascaded reservoirs promote phosphorus bioavailability of surface sediments in the Upper Mekong River - Zhengjian Yang; QiFeng Min; Xiaojuan Guo; Congfeng Wang; Bi'’e Yan; Xiaoling Li; Defu Liu; Jun Ma; Andreas Lorke (Science of The Total Environment, 2024)

Evaluation of water quality fluctuation in the tidal reach under the impact of on shore wastewater discharges based on MIKE 21 model in dongguan, China - Changzheng Wu; Jinquan Wan; Yishu Wang; Zhangqing Bi; Yan Wang; Xiuwen Ren (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Effects of protein grass hay as alternative feed resource on lamb's fattening performance and meat quality - Yanmei Zhang; Ruicong Ma; Bo Chen; Wei Zhou; Naifeng Zhang; Yan Tu; Qiyu Diao; Tao Ma; Huaisen Chen; Kai Chen; Hong Ma; Yajuan Guo; et al. (Meat Science, 2024)

Late Paleozoic–Early Mesozoic subduction history of Mudanjiang Ocean: New insights from greenschist in the Heilongjiang Complex, NE China - Simiao Wang; Yu Dong; Junhui Bi; Yan Jing; Wenchun Ge; Hao Yang; Jielu Yu; Zheng Ji (Lithos, 2024)

Bioaccumulation and toxicological effects of dietborne arsenic exposure on the apple snail (Pomacea canaliculata) - Xiaoyang Bi; Yanwei Liu; Yan Wang; Dongqin Li; Huashou Li; Rongliang Qiu; Guikui Chen (Journal of Hazardous Materials, 2024)

Late mesozoic exhumation of silurian – Devonian and permian Ni-Co sulfide deposits in the East Kunlun orogenic belt: Constraints from zircon fission track ages - Xueyu Yan; Yuxin Fan; Qingsong Cai; Minmin Gao; Dengdong Lu; Ke Bi; Chuanying Zhu; Mingjie Zhang; Ying Wang; Guangliang Yang; Xiaohu Li; Buqing Wang (Journal of Geochemical Exploration, 2024)

Gamification effects in green behaviors: A double-edged sword - Chongwu Bi; Dandan Zhang; Zhuo Sun; Yan Jin; Ruixian Yang (Journal of Cleaner Production, 2024)

Guanidinium-based 3D cationic covalent organic frameworks with different amino modifications for the efficient removal of hexafluorobisphenol A - Jing Zhang; Mengzi Bi; Chunxiao Wang; Yan Xia (Journal of Environmental Chemical Engineering, 2024)

Fine mapping and functional validation of the candidate gene BhGA2ox3 for fruit pedicel length in wax gourd (Benincasa hispida) - Yan Deng; Peng Wang; Wenhui Bai; Zhihao Chen; Zhikui Cheng; Liwen Su; Xianglei Chen; Yeshun Bi; Rongjin Feng; Zhengguo Liu (Theoretical and Applied Genetics, 2024)

Environmental factors influencing the development and spread of resistance in erythromycin-resistant streptococcus pneumoniae - Zhi-Hua Sun; Yi-Chang Zhao; Jia-Kai Li; Huai-yuan Liu; Wei Cao; Feng Yu; Bi-Kui Zhang; Miao Yan (Environmental Geochemistry and Health, 2024)

Creep mechanism of landslide formation in rock with bedding and weak layers in Zezhou, Shanxi, China - Zhiqiang Yi; Jianhui Long; Wenhui Shi; Hongyan Yan; Jining Zhang; Wenjun Bi; Yuqi Jin (Bulletin of Engineering Geology and the Environment, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

Can “ Zero waste city” policy promote green technology? Evidence from econometrics and machine learning - Shenghao Bi; Jianxiao Du; Zhenjun Yan; Andrea Appolloni (Journal of Environmental Management, 2024)

An alloying element screening method to design Zr2Co based alloys with superior disproportionation resistance - Yang Liu; Xuezhang Xiao; Zhiyi Yang; Fei Chu; Panpan Zhou; Jiapeng Bi; Tiao Ying; Xingwen Feng; Jiangfeng Song; Yan Shi; Changan Chen; Wenhua Luo; et al. (Chemical Engineering Journal, 2024)

Relevance and mechanism of STAT3/miR-221-3p/Fascin-1 axis in EGFR TKI resistance of triple-negative breast cancer - Lu-Lu Jin; Hua-Jun Lu; Jun-Kang Shao; Yan Wang; Shi-Ping Lu; Bi-Fei Huang; Gui-Nv Hu; Hong-Chuan Jin; Chao-Qun Wang (Molecular and Cellular Biochemistry, 2024)

Chronic environmental level exposure to perfluorooctane sulfonate overshadows graphene oxide to induce apoptosis through activation of the ROS-p53-caspase pathway in marine medaka Oryzias melastigma - Nan Xu; Xilin Jiang; Yan Liu; Muhammad Junaid; Manzoor Ahmad; Chunqing Bi; Wenjing Guo; Chen'ao Jiang; Shulin Liu (Chemosphere, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Advanced soft-sensing techniques for predicting furnace temperature in industrial organic waste gasification - Mingyue Yan; Huiyang Bi; HuanXu Wang; Caicai Xu; Lihao Chen; Lei Zhang; Shuangwei Chen; Xuming Xu; Qi Chen; Yingna Jia; Bo Wu; Zhongjian Li; et al. (Process Safety and Environmental Protection, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

Dexmedetomidine attenuates ferroptosis by Keap1-Nrf2/HO-1 pathway in LPS-induced acute kidney injury - Rui-Rui Luo; Jing Yang; Yan-Lin Sun; Bi-Ying Zhou; Si-Xuan Zhou; Guo-Xing Zhang; Ai-Xiang Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

DNA demethylase Tet2 promotes the terminal maturation of natural killer cells - Yuqing Lin; Biyun Yang; Hailin Liu; Guanghe Ran; Liang Song; Meng Meng; Xiaofeng Yin; Qinghua Bi; Dongmei Yan; Youcai Deng; Yonghui Lu (Immunologic Research, 2024)

Nontarget analysis and characterization of p-phenylenediamine-quinones and -phenols in tire rubbers by LC-HRMS and chemical species-specific algorithm - Caiming Tang; Yizhe Zhu; Ruifen Zheng; Ling Liu; Yan-Hong Zeng; Xiao-Jun Luo; Bi-Xian Mai (Analytica Chimica Acta, 2024)

Seasonally Changing Interactions of Species Traits of Termites and Trees Promote Complementarity in Coarse Wood Decomposition - Chao Guo; Bin Tuo; Sebastian Seibold; Hang Ci; Bi‐Le Sai; Han‐Tang Qin; En‐Rong Yan; Johannes H. C. Cornelissen (Ecology Letters, 2024)
Complementary resource use by functionally different species may accelerate ecosystem processes. However, how co‐variation in plant traits and animal traits promotes complementarity through temporal plant–animal interactions is poorly understood, even less so in detrital systems, thereby hampering our fundamental understanding of decomposition and carbon turnover. We hypothesised that, in seasonal subtropical forests where termites are major deadwood decomposers, trait complementarity of both termite species and tree species should promote overall deadwood decomposition through different seasons and years. Findings from a four‐year coarse wood decomposition experiment involving 27 tree and 5 termite species support this hypothesis. Phenological and mandibular traits of the two most abundant termite species controlled wood decomposition of tree species differing in wood traits, through the seasons over 4 years, thereby promoting overall deadwood decomposition rates. Our findings indicate that complementarity in functional trait co‐variation in plants and animals plays an important role in carbon cycling.

Investigating the 3D distribution of Cercospora leaf spot disease in sugar beet through fusion methods - Shunfu Xiao; Haochong Chen; Yaguang Hou; Ke Shao; Kaiyi Bi; Ruili Wang; Yang Sui; Jinyu Zhu; Yan Guo; Baoguo Li; Yuntao Ma (Computers and Electronics in Agriculture, 2024)

Insufficient KIF15 during porcine oocyte ageing induces HDAC6-based microtubule instability - Yan-Xuan Yin; Meng-Qi Ding; Yang Yi; Yuan-Jing Zou; Bi-Yun Liao; Shao-Chen Sun (Theriogenology, 2024)

Association of exposure to multiple metals with hemoglobin levels in Chinese children and adolescents - Fei Luo; Jianing Bi; Qing Liu; Gaojie Fan; Qing Fang; Xiya Qin; Xukuan Zhang; Xiaofeng Huang; Heng Li; Wenwen Guo; Binghai Liu; Lianyan Yan; et al. (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Metagenomics reveals the potential transmission risk of resistomes from urban park environment to human - Xiaochen Wang; Yuan Qian; Yu Wang; Sijie Wang; Jie Bi; Chenwei Shi; Qian Han; Ruijun Wan-Yan; Qiaoling Yu; Huan Li (Journal of Hazardous Materials, 2024)

Release of high-pressure hydrogen from type III tank in a fire scenario: Analysis and prediction of jet flame length and thermal response characteristics - Linzhi Zou; Bei Li; Bing Han; Yan Liu; Xueying Wang; Mingshu Bi; Chi-Min Shu (Fuel, 2024)

SS-CWGAN: A novel fault diagnosis model for building HVAC systems under limited labeled data - Mei Hua; Ke Yan; Jian Bi; Hua Wang (Energy and Buildings, 2024)

Amorphous bimetallic-organic framework enable accelerated redox kinetics and polysulfide trapping for lithium-sulfur batteries - Jingkun Bi; Lu Chen; Xiao Yan; Jian Guo; Ya Tang; Ma Jian; Shuo Meng; Kexuan Liao; Jia Yu; Wenli Yao; Ting He; Hongbin Zhao (Chemical Engineering Journal, 2024)

Three new isocoumarin analogues from an endolichenic fungus Aspergillus flavus CPCC 400810 - Ren-Zhong Wang; Bing-Jie Su; Yu-Chuan Chen; Tong-Mei Xiao; Bi-Ying Yan; Li-Yan Yu; Shu-Yi Si; De-Ling Wu; Ming-Hua Chen (Natural Product Research, 2024)

Transformer-based ozone multivariate prediction considering interpretable and priori knowledge: A case study of Beijing, China - Liangliang Mu; Suhuan Bi; Xiangqian Ding; Yan Xu (Journal of Environmental Management, 2024)

Antifungal activity of heat-treated wood extract against wood decay fungi - Zhenju Bi; Xinqi Gao; Jing Zhang; Yafang Lei; Li Yan (International Biodeterioration & Biodegradation, 2024)

Corrigendum to “Characterization of odor profiles of pea milk varieties and identification of key odor-active compounds by molecular sensory science approaches using soybean milk as a reference” [Food Chemistry 445(2024) 138696] - Lichang Yan; Ying Xu; Fan Yang; Chunhe Shi; Ye Liu; Shuang Bi (Food Chemistry, 2024)

Microbiome dynamics and environment driving factors throughout pit fermentation of Jiang-flavor Baijiu: A multi-omics study - Liangqiang Chen; Fangzhou Li; Fan Yang; Bi Chen; Hai Du; Li Wang; Yan Xu (Food Bioscience, 2024)

Self-centering concrete-filled steel tubular column-steel beam joint: Experiment and numerical modeling - Ben Mou; Xingchen Yan; Kaiming Bi; Wei Pan; Chang He (Engineering Structures, 2024)

Sponge iron-coupled biochar solution can achieve the synergistic augmentation of carbon sequestration, carbon sink capacity, and denitrification in ecological ditches - Bi–Ni Jiang; Ying–Ying Zhang; Yan Wang; Hai–qin Liu; Qing Zhou; Yi–Jing Yang; Zhi–Yong Zhang; Yu–Li Yang; Wen–jing Guo; Hai–Liang Song (Chemical Engineering Journal, 2024)

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

The migration and volatilization of toxic elements during briquette pyrolysis procedure - Juan Chen; Jianjun Wu; Yixin Zhang; Yang Guo; Long Yan; Jian Li; Zhenkun Guo; Bi Chen; Hua Wang (Minerals Engineering, 2024)

Effects of arsenic on gut microbiota and its bioaccumulation and biotransformation in freshwater invertebrate - Xiaoyang Bi; Yan Wang; Aiting Qiu; Shengze Wu; Wenhui Zhan; Hui Liu; Huashou Li; Rongliang Qiu; Guikui Chen (Journal of Hazardous Materials, 2024)

Mesozoic–Cenozoic exhumation of the giant Jinchuan Ni-Cu sulfide deposit, China: Evidence from single-grain apatite (U-Th)/He ages - Qingsong Cai; Xueyu Yan; Yuxin Fan; Minmin Gao; Guangliang Yang; Ke Bi; Ying Wang; Chuanying Zhu; Mingjie Zhang; Xiaohu Li (Journal of Asian Earth Sciences, 2024)

Characterization of odor profiles of pea milk varieties and identification of key odor-active compounds by molecular sensory science approaches using soybean milk as a reference - Lichang Yan; Ying Xu; Fan Yang; Chunhe Shi; Ye Liu; Shuang Bi (Food Chemistry, 2024)

Lamprey VDAC2: Suppressing hydrogen peroxide-induced 293T cell apoptosis by downregulating BAK expression - Mingjian Zhang; Wenwei Li; Xue Zhang; Mengfei Bi; Xinyu Wang; Feng Sun; Jiali Lu; Yan Chi; Yinglun Han; Qingwei Li; Tiesong Li (Fish & Shellfish Immunology, 2024)

Tetrabromobisphenol-A/S and their derivatives in surface particulates from workshop floors of three representative e-waste recycling sites in China - Hui Yang; Xiao-Jun Luo; Jia-Zhuo He; Yan-Hong Zeng; Bi-Xian Mai; Li-Zhong Wang; Xiang Bi (Environmental Research, 2024)

Achieving sustainable and highly efficient wood bonding through synergistic plant root-driven penetration mode with a hyperactive interface - Xiaoqian Bi; Yuan Zhang; Ping Li; Yan Wang; Yiqiang Wu; Yingfeng Zuo (Chemical Engineering Journal, 2024)

The characteristics of turbulence intermittency and its impact on surface energy imbalance over Loess Plateau - Heying Chang; Yan Ren; Hongsheng Zhang; Jiening Liang; Xianjie Cao; Pengfei Tian; Jiayun Li; Jianrong Bi; Lei Zhang (Agricultural and Forest Meteorology, 2024)

Climatic background of aeolian sand accumulation in the proximal sandy deserts/lands and its potential genetic linkage with loess in the Chinese Loess Plateau - Minmin Gao; Yuxin Fan; Qingsong Cai; Xueyu Yan; Ke Bi; Chuanying Zhu; Guangliang Yang; Qingsong Zhang (Quaternary International, 2024)

Study on transient temperature characteristics of SCR under different post-injection strategies - Xuexuan Nie; Yuhua Bi; Lizhong Shen; Shaohua Liu; Jie Yan; Size Zhang (Fuel, 2024)

The greener the living environment, the better the health? Examining the effects of multiple green exposure metrics on physical activity and health among young students - Yuheng Mao; Tianyu Xia; Fan Hu; Dan Chen; Yichen He; Xing Bi; Yangcen Zhang; Lu Cao; Jingheng Yan; Jinyu Hu; Yanzi Ren; Hongmei Xu; et al. (Environmental Research, 2024)

Seasonal coupling of iron (hydr-) oxides and organic carbon across elevations in Phragmites marshes of Yangtze Estuary - Yuxin Bi; Zhongzheng Yan; Wenzhen Zhao; Ying Lei; Tianyou Li; Liming Xue; Xiaoqing Gao; Xinhan Dong; Xiuzhen Li (CATENA, 2024)

Timp1 Deletion Induces Anxiety-like Behavior in Mice - Xiaotong Wang; Wei Zheng; Ziyi Zhu; Biyu Xing; Weijie Yan; Ke Zhu; Lingli Xiao; Chaojuan Yang; Mengping Wei; Lei Yang; Zi-Bing Jin; Xueyun Bi; et al. (Neuroscience Bulletin, 2024)

Mechanical characteristics and application of CFRP cable anchor support structures in coastal area - Zengming Hao; Nan Yan; Xiaoyu Bai; Lan Cui; Jichao Yin; Haojie Diao; Jinwei Bi; Junwei Liu (Ocean Engineering, 2024)

Fe(II)/Fe(III) cycle actuating a novel process to remove organics in waste pit mud from Maotai: Performance and mechanism - Yafei Yang; Jinlai Yuan; Guangxu Bi; Riyu Song; Hezhen Chen; Bi Chen; Fan Yang; Yan Wang; Li Wang (Journal of Water Process Engineering, 2024)

Enrichment process, structural prediction, isolation, in vitro cytotoxic and anti-inflammatory effects of triterpenoid saponins in Camellia japonica L. leaves water extract through UPLC-Q-TOF based mass spectrometry similarity networking - Hui Liu; Lisha Bi; Qirun Chen; Xiaozhi He; Huan Yan; Wei Ni; Wenjuan Wu; Li He; Haiyang Liu (Food Chemistry, 2024)

Flexible and wearable functional materials for ionizing radiation Protection: A perspective review - Hao Li; Linping Yan; Jibo Zhou; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2024)

Anti-epileptic and Neuroprotective Effects of Ultra-low Dose NADPH Oxidase Inhibitor Dextromethorphan on Kainic Acid-induced Chronic Temporal Lobe Epilepsy in Rats - Jing-Jing Yang; Ying-Xin Liu; Yan-Fang Wang; Bi-Ying Ge; Ying Wang; Qing-Shan Wang; Sheng Li; Jian-Jie Zhang; Ling-Ling Jin; Jau-Shyong Hong; Sheng-Ming Yin; Jie Zhao (Neuroscience Bulletin, 2024)

Extraction and analysis of the sea ice parameter dataset of the Bohai Sea from 2011 to 2021 based on GOCI - Ran Yan; Xi Zhang; Wenlong Bi; Ning Wang; Yiding Zhao; Luchuan Bi; Haipeng Guan; Yunbo Liu; Fuxi Duan; Meijie Liu (Frontiers in Marine Science, 2024)
The Bohai Sea and its surrounding areas are rich in oil and natural gas and play an important role in industry, agriculture and the economy. However, the Bohai Sea suffers severely from sea ice in the winter. While previous research has predominantly focused on methods for retrieving sea ice parameters in the Bohai Sea, analyses of their long-term statistical patterns have been limited. The Geostationary Ocean Color Imager (GOCI) is the first geostationary satellite for ocean color remote sensing, offering high spatial and temporal resolution, which greatly facilitates the extraction of Bohai Sea ice parameters. Utilizing GOCI data, we systematically extracted relevant sea ice parameters for the Bohai Sea region from 2011 to 2021. These parameters include sea ice concentration, sea ice thickness, and sea ice drift. We conducted a comprehensive statistical analysis of the long-term sea ice changes in the Bohai Sea and found that the development process of winter sea ice area is different from the sea ice thickness, and the direction of sea ice drift is basically unchanged. Then we developed statistical models linking sea ice parameters with ocean dynamic factors such as temperature, wind, and drift currents. Among them, the correlation coefficient between the predicted value and the measured value of the sea ice area model is the highest, reaching 0.8382. Furthermore, we examined the previously unexplored relationship between daily sea ice area, sea ice thickness, and accumulated temperature with their respective starting temperatures and accumulation periods. This study provides critical data to support Bohai Sea ice monitoring and marine environmental research. The results of this study contribute to a better understanding of sea ice change trends in the Bohai Sea and inform the development of disaster prevention and mitigation measures.

Overview of the recent advances in porcine epidemic diarrhea vaccines - Miao-Zhan Wei; Lan Chen; Rong Zhang; Ze Chen; Yan-Juan Shen; Bi-Jun Zhou; Kai-Gong Wang; Chun-Lan Shan; Er-Peng Zhu; Zhen-Tao Cheng (The Veterinary Journal, 2024)

Provenance of fine-grained sediments along the South Bohai Coast, China since the mid-Holocene, and its implications for understanding coastal evolution and anthropogenic influences - Xiao Sun; Yan Li; Liang Yi; Jingran Zhang; Jianhua Bi; Guangquan Chen; Ke Hu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A novel combined process for enhancing soluble salt recovery and reducing pollutant diffusion in municipal solid waste incineration fly ash - Xiaofan Huang; Lei Wang; Xiaotao Bi; Dahai Yan; Jonathan W.C. Wong; Yuezhao Zhu (Journal of Cleaner Production, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Characterization of DHA-enriched 1,3-unsaturated-2-palmitic acid triacylglycerol produced by Rhodococcus opacus cell factory - Linshang Zhang; Ke Yue; Hang Yang; Yingjing Bi; Lingzhi Cheong; Zipeng Yan; Yanlan Bi (Food Bioscience, 2024)

Transparent multifunctional cellulose-based conductive hydrogel for wearable strain sensors and arrays - Jianliang Gao; Xiaomeng Li; Lina Xu; Manqing Yan; Hong Bi; Qiyang Wang (Carbohydrate Polymers, 2024)

Bronchoalveolar Lavage Fluid Microbiota is Associated with the Diagnosis and Prognosis Evaluation of Lung Cancer - Chen Cheng; Zhifeng Wang; Chao Ding; Pingli Liu; Xiaoqiang Xu; Yan Li; Yi Yan; Xiaocong Yin; Bi Chen; Bing Gu (Phenomics, 2024)

New insights on intestinal microorganisms and carbohydrate metabolism in fish - Bi-Yun Zhang; Guo-He Cai; Hong-Ling Yang; Qing-Jie Nie; Zi-Yan Liu; Yun-Zhang Sun (Aquaculture International, 2024)

A New Method for the Correction of Spectrum Drift Caused by Temperature Changes When Using a NaI(Tl) Seawater Radioactivity Sensor - Yan Shi; Yingying Zhang; Xiandong Feng; Da Yuan; Bingwei Wu; Haijie Bi (Journal of Marine Science and Engineering, 2024)
The seawater radioactivity sensor based on the NaI(Tl) scintillation crystal detection method is prone to spectrum drift due to environment temperature changes during actual measurement, which pose difficulties in the activity analysis of seawater radionuclides. This paper adopts experiment design and analysis methods to study the relationship laws between temperature and peak position channel address and between gain and the peak position channel address. On the basis of studying and summarizing the two relationship laws of the NaI(Tl) seawater radioactivity sensor, a spectrum drift correction method combining gain adjustment and spectrum processing is proposed. Laboratory air and water environment experiments verify that the peak position channel address drift after air environment correction does not exceed ±2 channels, and after water environment correction does not exceed ±1 channel. Long-term verification experiments at the seawater work site have shown that this correction method can effectively correct the spectrum drift of the NaI(Tl) seawater radioactivity sensor and meet the requirements of long-term automatic operations at sea for the measured spectrum.

A proteomic study on gastric impairment in rats caused by microcystin-LR - Shang-Chun Li; Li-Hong Gu; Yan-Fang Wang; Li-Mei Wang; Liang Chen; John P. Giesy; Xun Tuo; Wen-Li Xu; Qian-Hui Wu; Yi-Qing Liu; Ming-Huo Wu; Yang-Yang Diao; et al. (Science of The Total Environment, 2024)

Nonlinear effects of surface soil moisture changes on vegetation greenness over the Tibetan plateau - Wenwen Li; Denghua Yan; Baisha Weng; Yuequn Lai; Lin Zhu; Tianling Qin; Zhaoyu Dong; Wuxia Bi (Remote Sensing of Environment, 2024)

Nickel oxide nanoparticles: A new generation nanoparticles to combat bacteria Xanthomonas oryzae pv. oryzae and enhance rice plant growth - Yasmine Abdallah; Solabomi Olaitan Ogunyemi; Ji'’an Bi; Fang Wang; Xuan Huang; Xianbo Shi; Jiefeng Jiang; Ezzeldin Ibrahim; Mohamed Mohany; Salim S. Al-Rejaie; Chengqi Yan; Bin Li (Pesticide Biochemistry and Physiology, 2024)

Remotely sensed retrieval of air-sea carbon flux and acidification risk in Chinese Bohai Sea based on a semi-analytical mechanism model with hour-level GOCI image and ERA5 reanalysis data - Xiang Yu; Yan Liu; Jialin Bi; Xiaoyu Cai; Liping Wang; Liangkun Nie; Chao Qiao; Guanghao Li; Chao Zhan; Guoqing Li; Xianbin Liu; Xiaohui Wang (Journal of Cleaner Production, 2024)

3D reconstruction and characterization of cotton bolls in situ based on UAV technology - Shunfu Xiao; Shuaipeng Fei; Yulu Ye; Demin Xu; Ziwen Xie; Kaiyi Bi; Yan Guo; Baoguo Li; Rui Zhang; Yuntao Ma (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Analyzing the correlation between quinolone-resistant Escherichia coli resistance rates and climate factors: A comprehensive analysis across 31 Chinese provinces - Yi-Chang Zhao; Zhi-Hua Sun; Ming-Xuan Xiao; Jia-Kai Li; Huai-yuan Liu; Hua-Lin Cai; Wei Cao; Yu Feng; Bi-Kui Zhang; Miao Yan (Environmental Research, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Steroidal saponins from the roots of Paris verticillata and their anti-proliferative and anti-inflammatory activities - Yan Liu; Yu Bi; Jin-Ting Bai; Si-Yi Wang; Jia-Tong Wu; Yi-Kai Jiang; Peng Jiang; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Phytochemistry, 2024)

Unveiling the nitrogen and phosphorus removal potential: Comparative analysis of three coastal wetland plant species in lab-scale constructed wetlands - Xiaoqing Gao; Yuxin Bi; Lin Su; Ying Lei; Lv Gong; Xinhan Dong; Xiuzhen Li; Zhongzheng Yan (Journal of Environmental Management, 2024)

Effect of corn stalks on coal catalytic hydrogasification in a pressurized fluidized bed for manufacturing CH4 - Shuai Yan; Jun Feng; Zihong Xia; Yingying Huang; Fengshuang Han; Xuan Qu; Jicheng Bi (Fuel, 2024)

A comprehensive assessment of external exposure to persistent halogenated organic pollutants for residents in an e-waste recycling site, South China - Yin-Zhi Lv; Xiao-Jun Luo; Xue-Meng Qi; Ke-Lan Guan; Yan-Hong Zeng; Bi-Xian Mai (Environmental Pollution, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

Adaptation of Ulva lactuca in low-salinity and high-nutrient water environment and its synergistic microbial effect on inorganic nitrogen removal - Jinxin Chen; Changzheng Wu; Jinquan Wan; Yan Wang; Bin Zhu; Xuejian Wang; Zhangqing Bi (Journal of Applied Phycology, 2024)

Summer surface warming driven by the strong El Niño in the South China Sea - Hanwen Bi; Qin-Yan Liu; Xianyao Chen (Climate Dynamics, 2024)

Characterization and stabilization of incineration fly ash from a new multi-source hazardous waste co-disposal system: field-scale study on solidification and stabilization - Xiaofan Huang; Lei Wang; Gu Fan; Xiaotao Bi; Dahai Yan; Jonathan W. C. Wong; Yuezhao Zhu (Environmental Science and Pollution Research, 2024)

Unveiling the impact of flooding and salinity on iron oxides-mediated binding of organic carbon in the rhizosphere of Scirpus mariqueter - Yuxin Bi; Xiaoqing Gao; Lin Su; Ying Lei; Tianyou Li; Xinhan Dong; Xiuzhen Li; Zhongzheng Yan (Science of The Total Environment, 2024)

The impact of extreme precipitation on physical and biogeochemical processes regarding with nutrient dynamics in a semi-closed bay - Rushui Xiao; Guandong Gao; Dezhou Yang; Ying Su; Yang Ding; Rong Bi; Shibo Yan; Baoshu Yin; Shengkang Liang; Xianqing Lv (Science of The Total Environment, 2024)

Bioaccumulation, tissue distributions, and maternal transfer of perfluoroalkyl carboxylates (PFCAs) in laying hens - Qun-Jie Feng; Xiao-Jun Luo; Mei-Xia Ye; Ke-Qi Hu; Yan-Hong Zeng; Bi-Xian Mai (Science of The Total Environment, 2023)

Expression of a periplasmic β-carbonic anhydrase (CA) gene is positively correlated with HCO3- utilization by the gametophytes of Saccharina japonica (Phaeophyceae, Ochrophyta) - Hui-Min Hao; Yan-Hui Bi; Ning-Ning Wei; Pei-Chong Lin; Shou-Hua Mei; Zhi-Gang Zhou (Journal of Applied Phycology, 2023)

Executive function elevated by long term high-intensity physical activity and the regulation role of beta-band activity in human frontal region - Junxiang Wang; Xudong Zhao; Yan Bi; Shan Jiang; Yinghua Sun; Jian Lang; Chuanliang Han (Cognitive Neurodynamics, 2023)

Behavior of traditional concrete dams and three-dimensional printed concrete dams under the debris flow impact - Hani Meree; Shuai-xing Yan; Dong-po Wang; Yu-zhang Bi (Journal of Mountain Science, 2023)

Label-free quantitative proteomic analysis of milk fat globule membrane proteins in porcine colostrum and mature milk - Huiwen Zhao; Mohan Li; Qing Zhu; Aicheng Liu; Jiayang Bi; Zhizhong Quan; Xue Luo; Yan Zheng; Ning Yang; Xiqing Yue; Xueyan Cao (Food Chemistry, 2023)

Towards a better understanding of the anaerobic/oxic/anoxic-aerobic granular sludge process (AOA-AGS) for simultaneous low-strength wastewater treatment and in situ sludge reduction from ambient to winter temperatures - Qiulai He; Xiaohui Yan; Hongyu Wang; Yaning Ji; Jinfeng Li; Liang Liu; Peng Bi; Peng Xu; Baokun Xu; Jingwei Ma (Environmental Research, 2023)

A multifunctional surgical suture with electroactivity assisted by oligochitosan/gelatin-tannic acid for promoting skin wound healing and controlling scar proliferation - Hui Han; Liqin Tang; Yan Li; Yong Li; Ming Bi; Jun Wang; Fujun Wang; Lu Wang; Jifu Mao (Carbohydrate Polymers, 2023)

Changed mercury speciation in clouds driven by changing cloud water chemistry and impacts on photoreduction: Field evidence at Mt. Tai in eastern China - Jiebo Zhen; Tao Li; Xinmiao Xu; Ping Du; Yue Song; Xiaoling Nie; Xinghui Liu; Hengde Liu; Yujian Bi; Xinfeng Wang; Likun Xue; Yan Wang (Water Research, 2023)

Paleozoic rapid denudation of the Proterozoic Jinchuan Ni-Cu-PGE sulfide deposit, NW China: Insights from single-grain zircon (U-Th)/He thermochronology - Qingsong Cai; Yuxin Fan; Xueyu Yan; Ying Wang; Minmin Gao; Guangliang Yang; Mingjie Zhang; Ke Bi; Hongfu Zhang; Xiaohu Li (Journal of Asian Earth Sciences, 2023)

Sedimentary evolution of the western North Yellow Sea mud patch: A Holocene perspective - Tianhao Yan; Houjie Wang; Lina Ai; Xiting Liu; Limin Hu; Naishuang Bi; Zongzhu Han; Xiao Wu (Continental Shelf Research, 2023)

Advanced low-strength wastewater treatment, side-stream phosphorus recovery, and in situ sludge reduction with aerobic granular sludge - Qiulai He; Xiaohui Yan; Zhiyi Xie; Peng Xu; Zhidong Fu; Jinfeng Li; Liang Liu; Peng Bi; Baokun Xu; Jingwei Ma (Bioresource Technology, 2023)

p-Nrf2/HO-1 Pathway Involved in Methamphetamine-induced Executive Dysfunction through Endoplasmic Reticulum Stress and Apoptosis in the Dorsal Striatum - Tao Wei; Jun-Da Li; Yu-Jing Wang; Wei Zhao; Fan Duan; Yan Wang; Ling-Ling Xia; Zhao-Bin Jiang; Xun Song; Yu-Qiong Zhu; Wen-Yi Shao; Ze Wang; et al. (Neurotoxicity Research, 2023)

Immobilization of chromium in real tannery sludge via heat treatment with coal fly ash - Yonglin Yang; Shuaige Shi; Chao Zhu; Xiangping Chen; Yongyong Hao; Long Yan; Jian Li; Xiaodong Chen; Bi Chen; Xiangrong Ma; Hongrui Ma (Chemosphere, 2023)

Gold nanocluster-confined covalent organic frameworks as bifunctional probes for electrochemiluminescence and colorimetric dual-response sensing of Pb2+ - Libo Li; Wanlin Zhao; Yan Wang; Xiaohong Liu; Panao Jiang; Lijun Luo; Xiaoya Bi; Xiangle Meng; Qijian Niu; Xiaofeng Wu; Tianyan You (Journal of Hazardous Materials, 2023)

Efficient photodegradation of micropollutants by tubular carbon nitride: The role of nitrogen defects - Lanbo Bi; Jimin Shen; Pengwei Yan; Gang Fu; Jiaxu Zhang; Jing Kang; Binyuan Wang; Linghan Li; Yanchi Zhou; Zhonglin Chen (Journal of Cleaner Production, 2023)

Integrated microbial electrolysis with high-alkali pretreated sludge digestion: Insight into the effect of voltage on methanogenesis and substrate metabolism - Ling Wang; Chang Liu; Thangavel Sangeetha; Wei Mon Yan; Fang Sun; Zhiling Li; Xiaodong Wang; Kailing Pan; Aijie Wang; Xuejun Bi; Wenzong Liu (Journal of Environmental Management, 2023)

Performance of anaerobic/oxic/anoxic simultaneous nitrification, denitrification and phosphorus removal system overwhelmingly dominated by Candidatus_Competibacter: Effect of aeration time - Jingwei Ma; Yaning Ji; Zhidong Fu; Xiaohui Yan; Peng Xu; Jinfeng Li; Liang Liu; Peng Bi; Liang Zhu; Baokun Xu; Qiulai He (Bioresource Technology, 2023)

Comparative transcriptome analysis of grafting to improve chilling tolerance of cucumber - Xin Fu; Chun-Yu Lv; Yan-Yan Zhang; Xi-Zhen Ai; Huan-Gai Bi (Protoplasma, 2023)

Heterologous expression of MiMLDP, a major lipid droplet protein of the microalga Myrmecia incisa, in Saccharomyces cerevisiae promotes more triacylglycerol storage principally by enlarging lipid droplet size - Jian-Min Hu; Zheng Sun; Qi-Hui Xu; Xiao-Peng Fang; Yan-Hui Bi; Zhi-Gang Zhou (Algal Research, 2023)

Numerical study in the pressure effects on coal catalytic hydrogasification in the bubbling fluidized bed - Zhipeng Yao; Xudong Song; Shuai Yan; Zihong Xia; Caixia Chen; Xuan Qu; Jicheng Bi (Fuel, 2023)

Circulating Plasma miRNA Homologs in Mice and Humans Reflect Familial Cerebral Cavernous Malformation Disease - Sharbel G. Romanos; Abhinav Srinath; Ying Li; Bingqing Xie; Chang Chen; Yan Li; Thomas Moore; Dehua Bi; Je Yeong Sone; Rhonda Lightle; Nick Hobson; Dongdong Zhang; et al. (Translational Stroke Research, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

High-throughput calculation of organ-scale traits with reconstructed accurate 3D canopy structures using a UAV RGB camera with an advanced cross-circling oblique route - Shunfu Xiao; Yulu Ye; Shuaipeng Fei; Haochong Chen; Bingyu zhang; Qing li; Zhibo Cai; Yingpu Che; Qing Wang; AbuZar Ghafoor; Kaiyi Bi; Ke Shao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Enhancement of the chemical stability of nanoemulsions loaded with curcumin by unsaturated mannuronate oligosaccharide - Decheng Bi; Meiting Li; Lijun Yao; Nanting Zhu; Weishan Fang; Wushuang Guo; Yan Wu; Hong Xu; Zhangli Hu; Xu Xu (Food Chemistry, 2023)

Preparation of P-doped biochar and its high-efficient removal of sulfamethoxazole from water: Adsorption mechanism, fixed-bed column and DFT study - Yizhen Cheng; Jingrui Yang; Jimin Shen; Pengwei Yan; Shan Liu; Jing Kang; Lanbo Bi; Binyuan Wang; Shengxin Zhao; Zhonglin Chen (Chemical Engineering Journal, 2023)

Research on the blocking effect of baffle-net structure on rock avalanches: consider the influence of particle splashing - Yu-Zhang Bi; Dong-Po Wang; Shuai-Xing Yan; Qin-Ze Li; Si-Ming He (Bulletin of Engineering Geology and the Environment, 2023)

Drought-flood abrupt alteration events over China - Wuxia Bi; Meng Li; Baisha Weng; Denghua Yan; Zhaoyu Dong; Jianming Feng; Hao Wang (Science of The Total Environment, 2023)

Integrative transcriptome and metabolome revealed the molecular mechanism of Bacillus megaterium BT22-mediated growth promotion in Arabidopsis thaliana - Xiao Liu; Yan Du; Xiaofan Na; Man Wang; Ying Qu; Linghui Ge; Yuanmeng Wang; Linqi Gao; Wenke Bai; Yurong Bi; Libin Zhou (Journal of Plant Physiology, 2023)

Soy protein isolate-polyguluronate nanoparticles loaded with resveratrol for effective treatment of colitis - Wenhao Li; Decheng Bi; Jiang Yi; Lijun Yao; Jue Cao; Peng Yang; Meiting Li; Yan Wu; Hong Xu; Zhangli Hu; Xu Xu (Food Chemistry, 2023)

Characteristics of microbial communities in fermentation of pickled ginger and their correlation with its volatile flavors - Yan Chen; Lei Chen; Lei Liu; Xiufang Bi; Xiaocui Liu (Food Bioscience, 2023)

Barbican-inspired bimetallic core–shell nanoparticles for fabricating natural leather-based radiation protective materials with enhanced X-ray shielding capability - Hao Li; Jibo Zhou; Linping Yan; Rui Zhong; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2023)

Iron plaque crystallinity, heavy metal toxicity, and metal translocation in Kandelia obovata seedlings as altered by an iron-reducing bacterium under different flooding regimes - Qiqiong Zhang; Zhongzheng Yan; Yuxin Bi; Ying Lei; Xiaoqing Gao; Xiuzhen Li; Hans Brix (Plant and Soil, 2023)

The study on Cu-ZK-5 catalyst of copper content regulation and anti-propylene poisoning mechanism in NH3-SCR reaction - Yuchao Zang; Yalian Bi; Caixia Liu; Yan Zhang; Qing Li; Yanhua Wang; Min Zhang; Qingling Liu; Ziyin Zhang (Fuel, 2023)

Trends of source apportioned PM2.5 in Tianjin over 2013–2019: Impacts of Clean Air Actions - Qili Dai; Jiajia Chen; Xuehan Wang; Tianjiao Dai; Yingze Tian; Xiaohui Bi; Guoliang Shi; Jianhui Wu; Baoshuang Liu; Yufen Zhang; Beizhan Yan; Patrick L. Kinney; et al. (Environmental Pollution, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Quercetin alleviates tubulointerstitial inflammation by inhibiting exosomes-mediated crosstalk between tubular epithelial cells and macrophages - Di Yin; Jing-Yuan Cao; Yan Yang; Zhong-Tang Li; Hong Liu; Tao-Tao Tang; Wei-Jie Ni; Yi-Lin Zhang; Wei Jiang; Yi Wen; Zuo-Lin Li; Jing Zhao; et al. (Inflammation Research, 2023)

Identification of potential necroinflammation-associated necroptosis-related biomarkers for delayed graft function and renal allograft failure: a machine learning-based exploration in the framework of predictive, preventive, and personalized medicine - Qing Bi; Ji-Yue Wu; Xue-Meng Qiu; Yu-Qing Li; Yu-Yao Yan; Ze-Jia Sun; Wei Wang (EPMA Journal, 2023)

Tracking the life-cycle greenhouse gas emissions of municipal solid waste incineration power plant: A case study in Shanghai - Xiaoqu Han; Hongzhang Chang; Chuan Wang; Jun Tai; Sotirios Karellas; Junjie Yan; Lijie Song; Zhujie Bi (Journal of Cleaner Production, 2023)

Catalytic performances of Cu-ZK-5 zeolites with different template agents in NH3-SCR - Yuchao Zang; Qing Li; Yalian Bi; Caixia Liu; Yan Zhang; Yanhua Wang; Min Zhang; Qingling Liu; Ziyin Zhang; Rui Han (Journal of Environmental Chemical Engineering, 2023)

An FE Simulation of the Fracture Characteristics of Blunt Rock Indenter Under Static and Harmonic Dynamic Loadings Using Cohesive Elements - Siqi Li; Zhuo Chen; Wei Li; Tie Yan; Fuqing Bi; Yeshuang Tong (Rock Mechanics and Rock Engineering, 2023)

Effect of baicalin supplementation on the growth, health, antioxidant and anti-inflammatory capacity, and immune function of preweaned calves - Fengming Hu; Yanliang Bi; Xueling Zheng; Meng Lu; Qiyu Diao; Yan Tu (Animal Feed Science and Technology, 2023)

Karyotype analysis of the brown seaweed Saccharina (or Laminaria) japonica - Yan-Hui Bi; Zhi Li; Zhi-Gang Zhou (Algal Research, 2023)

Simultaneous determination of dissolved organic nitrogen, nitrite, nitrate and ammonia using size exclusion chromatography coupled with nitrogen detector - Wen-Xiang Ji; Ye-Chao Tian; Min-Hui Cai; Bi-Cun Jiang; Shi Cheng; Yan Li; Qing Zhou; Bo-Qiang Li; Bai-Yang Chen; Xing Zheng; Wen-Tao Li; Ai-Min Li (Journal of Environmental Sciences, 2023)

Recycling and reuse performance of cobalt catalyst for coal hydrogasification - Jun Feng; Shuai Yan; Rong Zhang; Sumin Gu; Xuan Qu; Jicheng Bi (Fuel, 2023)

γ-Glutamylcysteine rescues mice from TNBS-driven inflammatory bowel disease through regulating macrophages polarization - Jinyi Zhou; Xintong Yan; Xiaowen Bi; Shuai Lu; Xianli Liu; Chen Yang; Yingying Shi; Lan Luo; Zhimin Yin (Inflammation Research, 2023)

Alleviating effects of zinc and 24-epibrassionlide on cadmium accumulation in rice plants under nitrogen application - Zunxin Wang; Yang Li; Mingsong Liu; Ying Yang; Rui Wang; Siyuan Chen; Zongmei Liu; Feiyu Yan; Xinhong Chen; Junguo Bi; Zhiyao Dong; Feibing Wang (Chemosphere, 2023)

Occurrence, spatial distribution, and risk assessment of short- and medium-chain chlorinated paraffins in sediment from black-odorous rivers across China - Ke-Lan Guan; Xiao-Jun Luo; Qi-Hong Lu; Chen-Chen Huang; Xue-Meng Qi; Yan-Hong Zeng; Bi-Xian Mai; Shan-Quan Wang (Chemosphere, 2023)

Synthesis of crown ether-based microporous organic networks: A new type of efficient adsorbents for chlorophenols - Yi-Xuan Wang; Yan-Ping Bi; Yuan-Yuan Cui; Cheng-Xiong Yang (Journal of Hazardous Materials, 2023)

Uncertainty investigation for the classification of rock micro-fracture types using acoustic emission parameters - Longjun Dong; Yihan Zhang; Shuijin Bi; Ju Ma; Yihao Yan; Heng Cao (International Journal of Rock Mechanics and Mining Sciences, 2023)

Prediction and scenario simulation of the carbon emissions of public buildings in the operation stage based on an energy audit in Xi'an, China - Junjie Zhang; Zengfeng Yan; Wenbei Bi; Pingan Ni; Fuming Lei; Shanshan Yao; Jiachen Lang (Energy Policy, 2023)

Preparation, characterization and immunomodulatory effects of unsaturated sulfated oligoguluronic acid - Decheng Bi; Jinfeng Huang; Jue Cao; Lijun Yao; Wushuang Guo; Zhenqing Zhang; Yan Wu; Hong Xu; Zhangli Hu; Xu Xu (Carbohydrate Polymers, 2023)

The accumulation of organic contaminants in hair with different biological characteristics - Bin Tang; Jing Zheng; Shi-Mao Xiong; Feng-Shan Cai; Min Li; Yan Ma; Bo Gao; Dong-Wei Du; Yun-Jiang Yu; Bi-Xian Mai (Chemosphere, 2023)

Acute polyethylene microplastic (PE-MPs) exposure activates the intestinal mucosal immune network pathway in adult zebrafish (Danio rerio) - Yin Yuan; Marisol S. Sepúlveda; Baoliang Bi; Yadong Huang; Lingfu Kong; Hui Yan; Yu Gao (Chemosphere, 2023)

Comparative analysis of nitrate evolution patterns during pollution episodes: Method development and results from Tianjin, China - Yafei Li; Yan Han; Simeng Ma; Yufen Zhang; Haoqi Wang; Jingyi Yang; Lu Yao; Xiaohui Bi; Jianhui Wu; Yinchang Feng (Science of The Total Environment, 2023)

Simultaneous removal of Arsenic(III) and Chromium(VI) over ZnFe2O4 {100}/{111} Z-scheme photocatalyst: Facet-dependent active site and overlooked As(III)/Cr(VI) complex - Dashi Lei; Lu Zhang; Huikun Yan; Yuhan Liu; Xiangyu Peng; Wei Xiao; Qiang Bi; Juanqin Xue; Yubin Wang (Journal of Cleaner Production, 2023)

Exploration of β-glucosidase-producing microorganisms community structure and key communities driving cellulose degradation during composting of pure corn straw by multi-interaction analysis - Yue Han; Wanying Liu; Nuo Chang; Lei Sun; Ayodeji Bello; Liting Deng; Liyan Zhao; Ugochi Uzoamaka Egbeagu; Bo Wang; Yan Zhao; Mingming Zhao; Ruixin Bi; et al. (Journal of Environmental Management, 2023)

Fetal exposure to organic contaminants revealed by infant hair: A preliminary study in south China - Feng-Shan Cai; Bin Tang; Jing Zheng; Xiao Yan; Wei-Keng Luo; Mian He; Xiao-Jun Luo; Ming-Zhong Ren; Yun-Jiang Yu; Bi-Xian Mai (Environmental Pollution, 2023)

Novel double perovskite Ca2Gd0.5Nb1-W5/6O6:0.5 Eu3+ red phosphors with excellent thermal stability and high color purity for white LEDs - Ying Xiang; Zhiyao Liu; Yu Gao; Lei Feng; Ting Zhou; Mengjiao Liu; Yan Zhao; Xin Lai; Jian Bi; Daojiang Gao (Chemical Engineering Journal, 2023)

Reduction/pH-responsive disassemblable MOF-microbial nanohybrid for targeted tumor penetration and synergistic therapy - Xuemei Zeng; Pengjie Li; Shuangqian Yan; Bi-Feng Liu (Chemical Engineering Journal, 2023)

Corrigendum to “Rapid start-up and stable operation of an aerobic/oxic/anoxic simultaneous nitrification, denitrification, and phosphorus removal reactor with no sludge discharge” [Bioresour. Technol. 362 (2022) 127777] - Qiulai He; Xiaohui Yan; Zhidong Fu; Yihang Zhang; Peng Bi; Xingliang Mo; Peng Xu; Jingwei Ma (Bioresource Technology, 2023)

Transmembrane protein 106C accelerates the progression of breast cancer through the activation of PI3K/AKT/mTOR signaling - Jian Shang; Xiu Liu; Yanqing Bi; LiXia Yan; Cuiping Tian; Yu Guan (Molecular & Cellular Toxicology, 2023)

A new insight into the emission source of DDT in indoor environment from rural area of South China and comprehensive human health exposure assessment - Yin-Zhi Lv; Xiao-Jun Luo; Qi-Qi Li; Yan Yang; Yan-Hong Zeng; Bi-Xian Mai (Environmental Science and Pollution Research, 2022)

Vacuum Foam Drying Method Improved the Thermal Stability and Long-Term Shelf Life of a Live Attenuated Newcastle Disease Virus Vaccine - Fang Lyu; Yan-hong Zhao; Yu Lu; Xiao-xin Zuo; Bi-hua Deng; Min-qian Zeng; Jun-ning Wang; Ademola Olaniran; Jibo Hou; Thandeka Khoza (AAPS PharmSciTech, 2022)

Alterations in gut microbiota and metabolites associated with altitude-induced cardiac hypertrophy in rats during hypobaric hypoxia challenge - Zhiyuan Pan; Yichen Hu; Zongyu Huang; Ni Han; Yan Li; Xiaomei Zhuang; Jiye Yin; Hui Peng; Quansheng Gao; Wenpeng Zhang; Yong Huang; Yujun Cui; et al. (Science China Life Sciences, 2022)

One-dimensional recoverable ZnFe2O4/C/MnO2/BiOI magnetic composite with enhanced photocatalytic performance for organic dyes degradation - Mingliang Ma; Yan Chen; Jiabin Jiang; Yuxin Bi; Zijian Liao; Yong Ma (Environmental Science and Pollution Research, 2022)

Correlation of Ferroptosis and Other Types of Cell Death in Neurodegenerative Diseases - Xiaoting Dang; Xuejie Huan; Xixun Du; Xi Chen; Mingxia Bi; Chunling Yan; Qian Jiao; Hong Jiang (Neuroscience Bulletin, 2022)

Retrieval of Remotely Sensed Sediment Grain Size Evolution Characteristics along the Southwest Coast of Laizhou Bay Based on Support Vector Machine Learning - Xiang Yu; Chao Zhan; Yan Liu; Jialin Bi; Guoqing Li; Buli Cui; Longsheng Wang; Xianbin Liu; Qing Wang (Journal of Marine Science and Engineering, 2022)
Grain size is the basic property of intertidal zone sediment. Grain size acts as an indicator of sedimentary processes and geomorphological evolution under human and nature interactions. The remote sensing technique provides an alternative for sediment grain-size parameter monitoring with the advantages of wide coverage and real-time surveying. This paper attempted to map the distributions of three sediment grain size contents and the mean grain size with multitemporal Landsat images along the southwestern coast of Laizhou Bay, China, from 1989 to 2015. Considering the low correlations between the measured reflectance and grain-size parameters, we used a support vector machine (SVM) to develop a nonlinear calibration model by taking several band indices as input variables. Then, the performance of the back propagation neural network (BPNN) was determined and discussed with that of the SVM. The SVM performed better than the BPNN in calibrating the four grain-size parameters based on a comparison of R2 and the root-mean-square error (RMSE). Moreover, an atmospheric correction algorithm originally proposed for case II water enabled the TM\ETM+ images to be precisely atmospherically corrected in this study. The SVM-mapped spatial-temporal grain-size variation showed a coarsening trend, which agreed with that obtained during in situ measurements in a former study. The changes in Yellow River discharge and precipitation associated with the coarsening trend were further analyzed. The yielded results showed that the coarsening trend and reduction in tidal flat area might be aggravated with overutilization. More reasonable planning would be necessary in this case.

Spatial-temporal distributions and influential factors of phthalate acid esters in sediments of three lakes in Inner Mongolia - Yan Ma; Tong Liu; Bo-Tao Zhang; Yan Liu; Peng Shao; Chen Sun; Yichen Zhang; Jiale Bi; Yunkai Dong; Shengrui Wang; Guoming Zhang (Environmental Science and Pollution Research, 2022)

A point cloud registration method based on dual quaternion description with point-linear feature constraints - Raobo Li; Xiping Yuan; Shu Gan; Rui Bi; Yan Guo; Sha Gao (International Journal of Remote Sensing, 2022)

Hippocampal SIRT1-Mediated Synaptic Plasticity and Glutamatergic Neuronal Excitability Are Involved in Prolonged Cognitive Dysfunction of Neonatal Rats Exposed to Propofol - Lin-Hui Ma; Jie Wan; Jing Yan; Ning Wang; Yan-Ping Liu; Hai-Bi Wang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2022)

Analysis of geomorphologic features of the circular structure in the south of Lufeng Dinosaur Valley - Hu Lin; Gan Shu; Yuan Xiping; Yang MingLong; Gao Sha; Bi Rui; Li Yan (Earth Science Informatics, 2022)

Ero1‐Pdi1 module‐catalysed dimerization of a nucleotide sugar transporter, FonNst2 , regulates virulence of Fusarium oxysporum on watermelon - Yizhou Gao; Xiaohui Xiong; Hui Wang; Jiajing Wang; Yan Bi; Yuqing Yan; Zhongye Cao; Dayong Li; Fengming Song (Environmental Microbiology, 2022)
Summary Fusarium oxysporum f. sp. niveum ( Fon ) is a soil‐borne fungus causing vascular Fusarium wilt on watermelon; however, the molecular network regulating Fon virulence remains to be elucidated. Here, we report the function and mechanism of nucleotide sugar transporters (Nsts) in Fon . Fon genome harbours nine FonNst genes with distinct functions in vegetative growth, asexual production, cell wall stress response and virulence. FonNst2 and FonNst3 are required for full virulence of Fon on watermelon and FonNst2 is mainly involved in fungal colonization of the plant tissues. FonNst2 and FonNst3 form homo‐ or hetero‐dimers but function independently in Fon virulence. FonNst2, which has UDP‐galactose transporter activity in yeast, interacts with FonEro1 and FonPdi1, both of which are required for full virulence of Fon . FonNst2, FonPdi1 and FonEro1 target to endoplasmic reticulum (ER) and are essential for ER homeostasis and function. FonEro1‐FonPdi1 module catalyses the dimerization of FonNst2, which is critical for Fon virulence. Undimerized FonNst2 is unstable and degraded via ER‐associated protein degradation in vivo . These data demonstrate that FonEro1‐FonPdi1 module‐catalysed dimerization of FonNst2 is critical for Fon virulence on watermelon and provide new insights into the regulation of virulence in plant fungal pathogens via disulfide bond formation of key pathogenicity factors.

Transition in tectonic regime from the Paleo-Asian Ocean to Paleo-Pacific Ocean: constraints from the Jurassic adakitic and I-type granites, and calc-alkaline diorites at the northern margin of the North China Craton - Yan Jing; Wen-Chun Ge; Yu Dong; Hao Yang; Zheng Ji; Jun-Hui Bi; Hong-Ying Zhou; De-He Xing (International Geology Review, 2022)

Discerning the Putative U and V Chromosomes of Saccharina japonica (Phaeophyta) by Cytogenetic Mapping of Sex-Linked Molecular Markers - Yu Du; Peng-Fei Liu; Zhi Li; Qian Zheng; Yan-Hui Bi; Zhi-Gang Zhou (Frontiers in Marine Science, 2022)
Saccharina japonica , an importantly industrial species in brown seaweeds, has a typical alternate life history of heteromorphic generations and UV sex determination system. But up to now, the sex chromosomes, U and V, in this kelp remain to be evidenced cytologically. In the present study, the female-linked (SJ-f_000170 and MSj68-58-2) and male-linked (SJ-13_001840 and MSj68-16-2) molecular markers developed on the basis of Ectocarpus sex-determining regions (SDRs) were selected after PCR amplification and Southern blotting analysis. Mono-color fluorescence in situ hybridization (FISH) to the kelp metaphase chromosomes with each of these confirmed sex-linked markers as a probe indicated that the hybridization signals were confined to either female or male gametophytes exclusively. The shape and size of hybridized chromosomes and the relative location of these sex-linked markers on them suggested that the marked chromosomes in a sex were the same, which was further confirmed by dual-color FISH observations. SJ-f_000170 and SJ-13_001840, corresponding to each sex, were therefore used to map the sporophyte metaphase chromosomes by dual-color FISH technique, and they were hybridized on different chromosomes as expected. The sporophyte metaphase chromosomes as hybridized by SJ-f_000170 and SJ-13_001840 resembled those in either female or male gametophytes, suggesting that they were the putative U and V, respectively, chromosomes in S . japonica . To further demonstrate the reliability of this inference, genomic information of the screened bacterial artificial chromosome (BAC) clones carrying two female-linked markers, for example, from the constructed BAC libraries of the kelp female gametophytes was provided. The insert sequencing of two selected BAC clones revealed that repetitive elements were rich whereas gene density was poor, which was characterized as non-recombining SDR sequences in brown seaweed Ectocarpus sp. and liverwort Marchantia polymorpha . The present study laid a solid foundation for unveiling the mystery of S . japonica sex chromosomes.

Dihydroartemisinin alleviates AngII-induced vascular smooth muscle cell proliferation and inflammatory response by blocking the FTO/NR4A3 axis - Yan-Bing Huo; Xiang Gao; Qi Peng; Qiang Nie; Wei Bi (Inflammation Research, 2022)

Selenium Attenuates S. aureus-Induced Inflammation by Regulation TLR2 Signaling Pathway and NLRP3 Inflammasome in RAW 264.7 Macrophages - Ming-Ji Wei; Zhen-Nan Wang; Yan Yang; Shu-Jiu Zhang; He Tang; Hui Li; Chong-Liang Bi (Biological Trace Element Research, 2022)

A 5′ tRNA-Ala-derived small RNA regulates anti-fungal defense in plants - Hanqing Gu; Bi Lian; Yuxiang Yuan; Ci Kong; Yan Li; Chang Liu; Yijun Qi (Science China Life Sciences, 2022)

Identification of MicroRNAs as potential biomarkers for detecting ischemic stroke - Kexin Li; Li Shen; Pingping Zheng; Yanjun Wang; Lijuan Wang; Xiaoli Meng; Yaogai Lv; Zhiqiang Xue; Xin Guo; Anning Zhang; Pan Pan; Chunli Bi; et al. (Genes & Genomics, 2022)

Impacts of soft soil compaction and groundwater extraction on subsidence in the Yellow River Delta - Yi Zhang; Haijun Huang; Yanxia Liu; Haibo Bi; Zehua Zhang; Kuifeng Wang; Liwen Yan (Marine Georesources & Geotechnology, 2021)

Retraction Note to: Lupeol enhances inhibitory effect of 5-fluorouracil on human gastric carcinoma cells - Yan Liu; Tingting Bi; Wei Dai; Gang Wang; Liqiang Qian; Genhai Shen; Quangen Gao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Retraction Note to: S-Adenosylmethionine synergistically enhances the antitumor effect of gemcitabine against pancreatic cancer through JAK2/STAT3 pathway - Yan Liu; Tingting Bi; Linxun Liu; Quangen Gao; Genhai Shen; Lei Qin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Vegetation restoration and agricultural management to mitigate nitrogen pollution in the surface waters of the Dan River, China - Wei Wang; Zhanbin Li; Peng Shi; Yan Zhang; Baozhu Pan; Peng Li; Shijie Ding; Jing Li; Zhilei Bi; Xiukang Wang (Environmental Science and Pollution Research, 2021)

Neuroanatomical correlates of self-awareness of highly practiced visuomotor skills - Junjun Li; Zhenglong Lin; Ran Tao; Min Xu; Shihong Kong; Hong-Yan Bi; Yang Yang (Brain Structure and Function, 2021)

Associations of Sleep Characteristics with Cerebrospinal Fluid sTREM2 in Cognitively Normal Older Adults: the CABLE Study - He-Ying Hu; Ling-Zhi Ma; Hao Hu; Yan-Lin Bi; Ya-Hui Ma; Xue-Ning Shen; Ya-Nan Ou; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Retraction Note to: Lupeol inhibits proliferation and induces apoptosis of human pancreatic cancer PCNA-1 cells through AKT/ERK pathways - Yan Liu; Tingting Bi; Gang Wang; Wei Dai; Guoliang Wu; Liqiang Qian; Quangen Gao; Genhai Shen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Genipin Attenuates Tau Phosphorylation and Aβ Levels in Cellular Models of Alzheimer’s Disease - Meiting Li; Nan Cai; Liang Gu; Lijun Yao; Decheng Bi; Weishan Fang; Zhijian Lin; Yan Wu; Hong Xu; Hui Li; Zhangli Hu; Xu Xu (Molecular Neurobiology, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

The impact of land use and socio-economic factors on ammonia nitrogen pollution in Weihe River watershed, China - Zhilei Bi; Yan Zhang; Peng Shi; Xin Zhang; Zexuan Shan; Lijiang Ren (Environmental Science and Pollution Research, 2021)

Development and application of a novel triplex protein microarray method for rapid detection of antibodies against avian influenza virus, Newcastle disease virus, and avian infectious bronchitis virus - Yuan Li; Jianhua Hu; Jing Lei; Wentao Fan; Zhenwei Bi; Suquan Song; Liping Yan (Archives of Virology, 2021)

Arbuscular mycorrhizal colonization rate of an exotic plant, Galinsoga quadriradiata, in mountain ranges changes with altitude - Gang Liu; Rui-Ling Liu; Wen-Gang Zhang; Ying-Bo Yang; Xiao-Qiong Bi; Ming-Zhu Li; Xiao-Yan Chen; Hua Nie; Zhi-Hong Zhu (Mycorrhiza, 2021)

Spatiotemporal characteristics of sea ice transport in the Baffin Bay and its association with atmospheric variability - Weifu Sun; Haibo Bi; Min Fu; Xi Liang; Yunhe Wang; Yu Liang; Jue Huang; Haijun Huang; Liwen Yan; Qinglong Yu; Shuang Liang (Acta Oceanologica Sinica, 2021)

Middle–late permian I-type granitoids from the Diaobingshan region in the northern margin of the North China Craton: insight into southward subduction of the Paleo–Asian Ocean - Yan Jing; Zheng Ji; Wen-Chun Ge; Yu Dong; Hao Yang; Jun-Hui Bi (International Geology Review, 2021)

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

Speciation Analysis of Chromium in Chromium-Enriched Yeast by Ion Chromatography-Inductively Coupled Plasma Mass Spectrometry - Shuang-Qing Zhang; Sui-Han Cheng; Shi Shen; Bi-Ying Luo; Yan Zhang (Biological Trace Element Research, 2021)

S-adenosylmethionine induces apoptosis and cycle arrest of gallbladder carcinoma cells by suppression of JAK2/STAT3 pathways - Yan Liu; Tingting Bi; Fukang Yuan; Xinbao Gao; Gaolei Jia; Zhilong Tian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Serological characteristics of COVID-19 patients - Mi Zhou; Jing Zhong; Lei Bi; Pengcheng Shang; Yan Xing; Bo Wang; Jianlan He; Ying Xu; Tao Luo; Maohua Ma; Qingfeng Li (Infectious Diseases, 2020)

Immunocytochemical Localization of the Kinetochore Protein Nuf2p on the Gametophyte Chromosomes of a Cultivar of Saccharina (Phaeophyta) - Wu-Shan Dong; Peng-Fei Liu; Yu Liu; Yu Du; Yan-Hui Bi; Zhi-Gang Zhou (Frontiers in Marine Science, 2020)

Alpinia oxyphylla–Schisandra chinensis Herb Pair Alleviates Amyloid-β Induced Cognitive Deficits via PI3K/Akt/Gsk-3β/CREB Pathway - Yu Qi; Huiting Jing; Xinhui Cheng; Tingxu Yan; Feng Xiao; Bo Wu; Kaishun Bi; Ying Jia (NeuroMolecular Medicine, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Wild or farmed? A pilot study on determining origin of wildlife meat using methylation rate of ACTN3 gene and American mink - Bi Xiao Wang; Yue Ma; Yan Hua; Yan Chun Xu; Shu Hui Yang (Mammal Research, 2020)

MPTP-Induced Impairment of Cardiovascular Function - Xiaoli Liu; Bo Wei; Qianqian Bi; Qihang Sun; Li Li; Jian He; Yuancheng Weng; Shenyan Zhang; Genxiang Mao; Yizhong Bao; Shu Wan; Xiao Z. Shen; et al. (Neurotoxicity Research, 2020)

Effect of Nitrate Ions on Acidithiobacillus ferrooxidans-Mediated Bio-oxidation of Ferrous Ions and Pyrite - Fen W. Liu; Xing X. Qiao; Ke Xing; Jing Shi; Li X. Zhou; Yan Dong; Wen L. Bi; Jian Zhang (Current Microbiology, 2020)

Dynamic amplification factors for a system with multiple-degrees-of-freedom - Zhang Chao; Hao Hong; Bi Kaiming; Yan Xueyuan (Earthquake Engineering and Engineering Vibration, 2020)

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

Wireless charging and shared autonomous battery electric vehicles (W+SABEV): synergies that accelerate sustainable mobility and greenhouse gas emission reduction - Zicheng Bi; Michael A. Reiner; Gregory A. Keoleian; Yan Zhou; Michael Wang; Zhenhong Lin (Mitigation and Adaptation Strategies for Global Change, 2020)

Nitric oxide and hydrogen peroxide increase glucose-6-phosphate dehydrogenase activities and expression upon drought stress in soybean roots - Xiaomin Wang; Mengjiao Ruan; Qi Wan; Wenliang He; Lei Yang; Xinyuan Liu; Li He; Lili Yan; Yurong Bi (Plant Cell Reports, 2020)

miR-663b promotes colorectal cancer progression by activating Ras/Raf signaling through downregulation of TNK1 - Sen Hong; Zhenkun Yan; Helei Wang; Lei Ding; Yumei Song; Miaomiao Bi (Human Cell, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Population status and distribution of whitespotted conger ( Conger myriaster ) in Yellow Sea: An important migratory species along coastal China with limited data - Min Li; Yan Jiao; Rujia Bi; Yiping Ren (Fisheries Oceanography, 2020)
Whitespotted conger ( Conger myriaster ) is a marine migratory species with important economic and ecological values in Northwestern Pacific. The population status and distribution of whitespotted conger may have changed in the eastern coastal water of China owing to the intensive fishing pressure and human activities in the past few decades. There have been miscellaneous concerns about its population trend and potential environment‐driven variations in spatiotemporal distribution. Delta‐generalized linear models, generalized linear mixed models, and a set of correlation analyses were performed to answer the above concerns, and a stratified random sampling‐designed bottom trawl survey from 2011 to 2017 in Haizhou Bay of the central Yellow Sea was conducted to collect samples. Our study suggested that whitespotted conger remained a relatively stable population status with slight fluctuations likely caused by climate variability during 2011–2017. The hierarchical generalized linear mixed models with spatial random effect performed better than the generalized linear model and the common generalized linear mixed models. Spatiotemporal differences of whitespotted conger were significantly associated with bottom water salinity, depth, sampling time, and space, which were probably mainly influenced by a combination of the Cold Water Mass, the Yellow Sea Warm Current, and the Yellow Sea Coastal Current. The predicted spatiotemporal distribution of whitespotted conger has a monthly variation matching its seasonable migration and an overall higher abundance in the deeper water than that in the neritic areas in Haizhou Bay.

Combination of schisandrin and nootkatone exerts neuroprotective effect in Alzheimer’s disease mice model - Yu Qi; Xinhui Cheng; Huiting Jing; Tingxu Yan; Feng Xiao; Bo Wu; Kaishun Bi; Ying Jia (Metabolic Brain Disease, 2019)

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Time-domain denoising of time—frequency electromagnetic data - Bi-Ming Zhang; Shi-Kun Dai; Qi-Yun Jiang; Jian Yan; Guang Li (Applied Geophysics, 2019)

The Inhibitory Effects of Nitrogen Deposition on Asymbiotic Nitrogen Fixation are Divergent Between a Tropical and a Temperate Forest - Mianhai Zheng; Wei Zhang; Yiqi Luo; Shiqiang Wan; Shenglei Fu; Senhao Wang; Nan Liu; Qing Ye; Junhua Yan; Bi Zou; Chengliang Fang; Yuxi Ju; et al. (Ecosystems, 2019)

Feeding modes shape the acquisition and structure of the initial gut microbiota in newborn lambs - Yanliang Bi; Madison S. Cox; Fan Zhang; Garret Suen; Naifeng Zhang; Yan Tu; Qiyu Diao (Environmental Microbiology, 2019)
Summary Early gut microbial colonization is important for postnatal metabolic and immune development. However, little is known about the effects of different feeding modes (suckling versus bottle‐feeding) or microbial sources on this process in farm animals. We found that suckled and bottle‐fed newborn lambs had their own distinct gut microbiota. Results from 16S rRNA gene sequencing and qPCR showed that, compared with suckling, bottle feeding significantly increased the abundances of Escherichia/Shigella , Butyricicoccus , and Clostridium XlVa, while significantly decreased the abundance of Clostridium XI. The higher levels of Escherichia/Shigella in bottle‐fed lambs suggest that artificial feeding may increase the number of potential pathogens and delay the establishment of the anaerobic environment and anaerobic microbes. Feeding modes also affected the direct transmission of bacteria from the mother and the environment to newborns. The SourceTracker analysis estimated that the early gut microbes of suckled lambs were mainly derived from the mother's teats (43%) and ambient air (28%); whereas those of bottle‐fed lambs were dominated by bacteria from the mother's vagina (46%), ambient air (31%), and the sheep pen floor (12%). These findings advance our understanding of gut microbiota in early life and may help design techniques to improve gut microbiota and health.

The study of time domain denoising for the time-frequency electromagnetic method prospecting data - bi-ming Zhang; shi-kun Dai; qi-yun Jiang; jian Yan; guang Li (Applied Geophysics, 2019)

The Characteristics of Climate Change and Adaptability Assessment of Migratory Bird Habitats in Wolonghu Wetlands - Jun Ma; Baisha Weng; Wuxia Bi; Dengming Yan; Meng Li; Ting Xu; Lina Wang; Lin Wang (Wetlands, 2019)

RETRACTED ARTICLE: S-Adenosylmethionine synergistically enhances the antitumor effect of gemcitabine against pancreatic cancer through JAK2/STAT3 pathway - Yan Liu; Tingting Bi; Linxun Liu; Quangen Gao; Genhai Shen; Lei Qin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Long-term observation of cyanobacteria blooms using multi-source satellite images: a case study on a cloudy and rainy lake - Meng Mu; Chuanqing Wu; Yunmei Li; Heng Lyu; Shengzhong Fang; Xiang Yan; Ge Liu; Zhubin Zheng; Chenggong Du; Shun Bi (Environmental Science and Pollution Research, 2019)

A Smart Fluorescent Probe Based on Salicylaldehyde Schiff’s Base with AIE and ESIPT Characteristics for the Detections of N2H4 and ClO− - Ya Xie; Liqiang Yan; Yujian Tang; Minghui Tang; Shaoyang Wang; Li Bi; Wanying Sun; Jianping Li (Journal of Fluorescence, 2019)

Nonlinear joint PP-PS AVO inversion based on improved Bayesian inference and LSSVM - Wei Xie; Yan-Chun Wang; Xue-Qing Liu; Chen-Chen Bi; Feng-Qi Zhang; Yuan Fang; Azeem Tahir (Applied Geophysics, 2019)

Integrin-interacting protein Kindlin-2 induces mammary tumors in transgenic mice - Bing Li; Xiaochun Chi; Jiagui Song; Yan Tang; Juan Du; Xiaokun He; Xiaoran Sun; Zhenwu Bi; Yunling Wang; Jun Zhan; Hongquan Zhang (Science China Life Sciences, 2019)

Numerical investigation of effects of “baffles - deceleration strip” hybrid system on rock avalanches - Yu-zhang Bi; Si-ming He; Yan-jun Du; Jie Shan; Shuai-xing Yan; Dong-po Wang; Xin-po Sun (Journal of Mountain Science, 2019)

Flavonoid glucosides from the flowers of Trollius chinensis Bunge - Rui Yan; Yida Cui; Bowen Deng; Jiayi Bi; Guogang Zhang (Journal of Natural Medicines, 2019)

LysM1 in MmLYK2 is a motif required for the interaction of MmLYP1 and MmLYK2 in the chitin signaling - Zhiyuan Lv; Yan Huang; Bi Ma; Zhonghuai Xiang; Ningjia He (Plant Cell Reports, 2018)

Spatial and temporal variability of soil moisture based on multifractal analysis - Baisha Weng; Wuxia Bi; Zhixuan Zhao; Ting Xu; Dengming Yan (Arabian Journal of Geosciences, 2018)

Neuroprotective effects of nootkatone from Alpiniae oxyphyllae Fructus against amyloid-β-induced cognitive impairment - Bosai He; Fanxing Xu; Feng Xiao; Tingxu Yan; Bo Wu; Kaishun Bi; Ying Jia (Metabolic Brain Disease, 2018)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

CASCIRE surveillance network and work on avian influenza viruses - Yuhai Bi; Weifeng Shi; Jianjun Chen; Quanjiao Chen; Zhenghai Ma; Gary Wong; Wenxia Tian; Renfu Yin; Guanghua Fu; Yongchun Yang; William J. Liu; Chuansong Quan; et al. (Science China Life Sciences, 2017)

Characterization and physical mapping of nuclear ribosomal RNA (rRNA) genes in the haploid gametophytes of Saccharina japonica (Phaeophyta) - Li Liu; Qi-Fan Yang; Wu-Shan Dong; Yan-Hui Bi; Zhi-Gang Zhou (Journal of Applied Phycology, 2017)

Antioxidant activity of alcohol aqueous extracts of Crypthecodinium cohnii and Schizochytrium sp. - Jin-hui Yu; Yu Wang; Jie Sun; Fei Bian; Gao Chen; Yan Zhang; Yu-ping Bi; Ying-jie Wu (Journal of Zhejiang University-SCIENCE B, 2017)

Efficacy and safety of metformin and sitagliptin based triple antihyperglycemic therapy (STRATEGY): a multicenter, randomized, controlled, non-inferiority clinical trial - Wen Xu; Yiming Mu; Jiajun Zhao; Dalong Zhu; Qiuhe Ji; Zhiguang Zhou; Bin Yao; Anhua Mao; Samuel S. Engel; Bin Zhao; Yan Bi; Longyi Zeng; et al. (Science China Life Sciences, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

A Fluoro-Chromogenic Sensor Based on Organic Molecular Framework for Cu2+ and F− in Aqueous Soluble DMSO - Veikko Uahengo; Yan Zhang; Bi Xiong; Pingping Zhao; Ping Cai; Lydia Rhyman; Ponnadurai Ramasami; Kai Hu; Gongzhen Cheng (Journal of Fluorescence, 2017)

Hepatic expression of transcription factors affecting developmental regulation of UGT1A1 in the Han Chinese population - Ya-li Nie; Hang He; Jiang-feng Li; Xiang-guang Meng; Liang Yan; Pei Wang; Shu-jie Wang; Hong-zheng Bi; Li-rong Zhang; Quan-cheng Kan (European Journal of Clinical Pharmacology, 2017)

Arctic sea ice volume export through the Fram Strait from combined satellite and model data: 1979–2012 - Zehua Zhang; Haibo Bi; Ke Sun; Haijun Huang; Yanxia Liu; Liwen Yan (Acta Oceanologica Sinica, 2017)

Oxymatrine synergistically enhances antitumor activity of oxaliplatin in colon carcinoma through PI3K/AKT/mTOR pathway - Yan Liu; Tingting Bi; Zheng Wang; Guoliang Wu; Liqiang Qian; Quangen Gao; Genhai Shen (Apoptosis, 2016)

High-density marker profiling confirms ancestral genomes of Avena species and identifies D-genome chromosomes of hexaploid oat - Honghai Yan; Wubishet A. Bekele; Charlene P. Wight; Yuanying Peng; Tim Langdon; Robert G. Latta; Yong-Bi Fu; Axel Diederichsen; Catherine J. Howarth; Eric N. Jellen; Brian Boyle; Yuming Wei; et al. (Theoretical and Applied Genetics, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Erratum to: Simulation on Vibration Characteristics of Fractured Rock - Siqi Li; Tie Yan; Wei Li; Fuqing Bi (Rock Mechanics and Rock Engineering, 2016)

Genome-wide study refines the quantitative trait locus for number of ribs in a Large White × Minzhu intercross pig population and reveals a new candidate gene - Long-Chao Zhang; Jing-Wei Yue; Lei Pu; Li-Gang Wang; Xin Liu; Jing Liang; Hua Yan; Ke-Bin Zhao; Na Li; Hui-Bi Shi; Yue-Bo Zhang; Li-Xian Wang (Molecular Genetics and Genomics, 2016)

Programmed cell death in the cyanobacterium Microcystis aeruginosa induced by allelopathic effect of submerged macrophyte Myriophyllum spicatum in co-culture system - Yan He; Qiao-Hong Zhou; Bi-Yun Liu; Long Cheng; Yun Tian; Yong-Yuan Zhang; Zhen-Bin Wu (Journal of Applied Phycology, 2016)

Activation of phenylpropanoid pathway and PR of potato tuber against Fusarium sulphureum by fungal elicitor from Trichothecium roseum - Xiao-yan Yu; Yang Bi; Lu Yan; Xiao Liu; Yi Wang; Ke-ping Shen; Yong-cai Li (World Journal of Microbiology and Biotechnology, 2016)

Seafood consumption among Chinese coastal residents and health risk assessment of heavy metals in seafood - Ran Zhao; Shuangshuang Yan; Min Liu; Bi Wang; Dong Hu; Dongbei Guo; Juan Wang; Wanting Xu; Chun Fan (Environmental Science and Pollution Research, 2016)

Effects of suspended culture of the seaweed Laminaria japonica aresch on the flow structure and sedimentation processes - Zehua Zhang; Haijun Huang; Yanxia Liu; Liwen Yan; Haibo Bi (Journal of Ocean University of China, 2016)

Two new compounds from the roots of Ilex pubescens and their cytotoxic activity - Huan Xiong; Fang Zhao; Jiayi Bi; Yang Zhang; Guiyun Zhao; Xue Chen; Yuncong Li; Rui Yan; Qiang Zhao; Hua Qiao; Guogang Zhang (Journal of Natural Medicines, 2016)

Lignans from Schisandra chinensis ameliorate cognition deficits and attenuate brain oxidative damage induced by D-galactose in rats - Tingxu Yan; Lei Shang; Mengshi Wang; Chenning Zhang; Xu Zhao; Kaishun Bi; Ying Jia (Metabolic Brain Disease, 2016)

Characterization of the relationship between vascular bundles features and indica-allelic frequency using a seventh filial generations of indica × japonica rice crosses - Tiansheng Liu; Wenjing Bi; Jia Zhang; Yue Cui; Zhiqiang Yan; Yuanzheng Wang; Cheng Fei; Hai Xu; Liang Tang; Wenfu Chen; Jian Sun; Quan Xu (Euphytica, 2016)

Dispersion function of Rayleigh waves in porous layered half-space system - Shou-Guo Yan; Fu-Li Xie; Chang-Zheng Li; Bi-Xing Zhang (Applied Geophysics, 2016)

RETRACTED ARTICLE: Lupeol enhances inhibitory effect of 5-fluorouracil on human gastric carcinoma cells - Yan Liu; Tingting Bi; Wei Dai; Gang Wang; Liqiang Qian; Genhai Shen; Quangen Gao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Interleukin-22 promotes lung cancer cell proliferation and migration via the IL-22R1/STAT3 and IL-22R1/AKT signaling pathways - Yi Bi; Jingyan Cao; Shi Jin; Liyan Lv; Li Qi; Fang Liu; Jianxiong Geng; Yan Yu (Molecular and Cellular Biochemistry, 2016)

Seasonal variations in biochemical composition during the reproductive cycle of the veined rapa whelk Rapana venosa (Valenciennes, 1846) from the northern coast of China - Jinhong Bi; Qi Li; Hong Yu; Zhixin Zhang; Yan Lian; Renjie Wang; Tingyu Wang (Marine Biology Research, 2016)

Simulation on Vibration Characteristics of Fractured Rock - Siqi Li; Tie Yan; Wei Li; Fuqing Bi (Rock Mechanics and Rock Engineering, 2016)

Metabonomic Study of Biochemical Changes in Human Hair of Heroin Abusers by Liquid Chromatography Coupled with Ion Trap-Time of Flight Mass Spectrometry - Pu Xie; Tie-jie Wang; Guo Yin; Yan Yan; Li-he Xiao; Qing Li; Kai-shun Bi (Journal of Molecular Neuroscience, 2016)

Disruption of thalamic connectivity in Alzheimer’s disease: a diffusion tensor imaging study - Qing-Yong Zhu; Si-Wei Bi; Xiu-Ting Yao; Zhi-Yan Ni; Ying Li; Bo-Yu Chen; Guo-Guang Fan; Xiu-Li Shang (Metabolic Brain Disease, 2015)

Salvianolic acid A attenuates TNF-α- and d-GalN-induced ER stress-mediated and mitochondrial-dependent apoptosis by modulating Bax/Bcl-2 ratio and calcium release in hepatocyte LO2 cells - Xiaojing Yan; Zequn Jiang; Lei Bi; Ye Yang; Weiping Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Bioaccumulative characteristics of tetrabromobisphenol A and hexabromocyclododecanes in multi-tissues of prey and predator fish from an e-waste site, South China - Bin Tang; Yan-Hong Zeng; Xiao-Jun Luo; Xiao-Bo Zheng; Bi-Xian Mai (Environmental Science and Pollution Research, 2015)

Combining Bone Marrow Stromal Cells with Green Tea Polyphenols Attenuates the Blood-Spinal Cord Barrier Permeability in Rats with Compression Spinal Cord Injury - De-shui Yu; Li-bo Liu; Yang Cao; Yan-song Wang; Yun-long Bi; Zi-jian Wei; Song-ming Tong; Gang Lv; Xi-fan Mei (Journal of Molecular Neuroscience, 2015)

TaUBA, a UBA domain-containing protein in wheat (Triticum aestivum L.), is a negative regulator of salt and drought stress response in transgenic Arabidopsis - Xiao Li; Shuang-shuang Zhang; Jun-xia Ma; Guang-yan Guo; Xue-yong Zhang; Xu Liu; Cai-li Bi (Plant Cell Reports, 2015)

Projecting Future Transmission of Malaria Under Climate Change Scenarios: Challenges and Research Needs - Weiwei Yu; Kerrie Mengersen; Pat Dale; Xiaofang Ye; Yuming Guo; Lyle Turner; Xiaoyu Wang; Yan Bi; William J. H. McBride; John S. Mackenzie; Shilu Tong (Critical Reviews in Environmental Science and Technology, 2015)

Vitamin A Deficiency Impairs Spatial Learning and Memory: The Mechanism of Abnormal CBP-Dependent Histone Acetylation Regulated by Retinoic Acid Receptor Alpha - Nali Hou; Lan Ren; Min Gong; Yang Bi; Yan Gu; Zhifang Dong; Youxue Liu; Jie Chen; Tingyu Li (Molecular Neurobiology, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Gastropulmonary Route of Infection and the Prevalence of Microaspiration in the Elderly Patients with Ventilator-Associated Pneumonia Verified by Molecular Microbiology-GM-PFGE - Qing-hua Liu; Jing Zhang; Dian-jie Lin; Xiao-yan Mou; Li-xian He; Jie-ming Qu; Hua-yin Li; Bi-jie Hu; Ying-min Zhu; Du-ming Zhu; Xiao-dong Gao (Cell Biochemistry and Biophysics, 2015)

RETRACTED ARTICLE: Lupeol inhibits proliferation and induces apoptosis of human pancreatic cancer PCNA-1 cells through AKT/ERK pathways - Yan Liu; Tingting Bi; Gang Wang; Wei Dai; Guoliang Wu; Liqiang Qian; Quangen Gao; Genhai Shen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Advances in alternating electromagnetic field data processing for earthquake monitoring in China - GuoZe Zhao; YaXin Bi; LiFeng Wang; Bing Han; Xiao Wang; QiBin Xiao; JunTao Cai; Yan Zhan; XiaoBin Chen; Ji Tang; JiJun Wang (Science China Earth Sciences, 2015)

l-Ornithine Schiff base–copper and –cadmium complexes as new proteasome inhibitors and apoptosis inducers in human cancer cells - Zhongyu Zhang; Caifeng Bi; Yuhua Fan; Nan Zhang; Rahul Deshmukh; Xingchen Yan; Xiuwen Lv; Pengfei Zhang; Xia Zhang; Q. Ping Dou (JBIC Journal of Biological Inorganic Chemistry, 2015)

Improved synthesis of phosphatidylserine using bio-based solvents, limonene and p-cymene - Yan-Hong Bi; Zhang-Qun Duan; Wen-Ying Du; Zhao-Yu Wang (Biotechnology Letters, 2015)

Molecular characterization of a novel reovirus isolated from Pekin ducklings in China - Ying-Qi Zhu; Chuan-Feng Li; Zhuang-Li Bi; Zong-Yan Chen; Chun-Chun Meng; Gui-Jun Wang; Chan Ding; Guang-Qing Liu (Archives of Virology, 2015)

An Arctic sea ice thickness variability revealed from satellite altimetric measurements - Haibo Bi; Haijun Huang; Qiao Su; Liwen Yan; Yanxia Liu; Xiuli Xu (Acta Oceanologica Sinica, 2014)

Effects of dietary amylose/amylopectin ratio on growth performance, feed utilization, digestive enzymes, and postprandial metabolic responses in juvenile obscure puffer Takifugu obscurus - Xiang-he Liu; Chao-xia Ye; Ji-dan Ye; Bi-duan Shen; Chun-yan Wang; An-li Wang (Fish Physiology and Biochemistry, 2014)

Species-Specific Bioaccumulation of Halogenated Organic Pollutants and Their Metabolites in Fish Serum from an E-Waste Site, South China - Yan-Hong Zeng; Xiao-Jun Luo; Xiao-Bo Zheng; Bin Tang; Jiang-Ping Wu; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Predicting DNA-binding sites of proteins based on sequential and 3D structural information - Bi-Qing Li; Kai-Yan Feng; Juan Ding; Yu-Dong Cai (Molecular Genetics and Genomics, 2014)

Vibrio harveyi as a causative agent of mass mortalities of megalopa in the seed production of swimming crab Portunus trituberculatus - Xiao-Jun Zhang; Xue-Song Bai; Bin-Lun Yan; Ke-Ran Bi; Lei Qin (Aquaculture International, 2014)

The impact of heat waves on children’s health: a systematic review - Zhiwei Xu; Perry E. Sheffield; Hong Su; Xiaoyu Wang; Yan Bi; Shilu Tong (International Journal of Biometeorology, 2014)

Probing the distribution and contamination levels of 10 trace metal/metalloids in soils near a Pb/Zn smelter in Middle China - Zhonggen Li; Xinbin Feng; Xiangyang Bi; Guanghui Li; Yan Lin; Guangyi Sun (Environmental Science and Pollution Research, 2014)

Sex identification and genetic variation of Saccharina (Phaeophyta) gametophytes as revealed by inter-simple sequence repeat (ISSR) markers - Jun-Gang Gu; Yu-Ping Sun; Yu Liu; Yan-Hui Bi; Zhi-Gang Zhou (Journal of Applied Phycology, 2014)

Development and Characterisation of Ursolic Acid Nanocrystals Without Stabiliser Having Improved Dissolution Rate and In Vitro Anticancer Activity - Ju Song; Yancai Wang; Yuelin Song; Hokman Chan; Chao Bi; Xiao Yang; Ru Yan; Yitao Wang; Ying Zheng (AAPS PharmSciTech, 2014)

Synthesis and antibacterial evaluation of furan derivatives bearing a rhodanine moiety - Jian Che; Chang-Ji Zheng; Ming-Xia Song; Ya-Jing Bi; Yi Liu; Yin-Jing Li; Yan Wu; Liang-Peng Sun; Hu-Ri Piao (Medicinal Chemistry Research, 2014)

Identification of MV-generated ROS responsive EST clones in floral buds of Litchi chinensis Sonn. - Wei-Wei Liu; Hye-Ji Kim; Hou-Bin Chen; Xing-Yu Lu; Bi-Yan Zhou (Plant Cell Reports, 2013)

Relationship between gene polymorphisms of two cytokine genes (TNF-α and IL-6) and occurring of lung cancers in the ethnic group Han of China - Jing Liang; Xiaolin Liu; Zhenqiang Bi; Beibei Yin; Junjuan Xiao; Hairong Liu; Yan Li (Molecular Biology Reports, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

Aggravated inflammation and increased expression of cysteinyl leukotriene receptors in the brain after focal cerebral ischemia in AQP4-deficient mice - Wen-Zhen Shi; Chun-Zhen Zhao; Bing Zhao; Qiao-Juan Shi; Li-Hui Zhang; Yan-Fang Wang; San-Hua Fang; Yun-Bi Lu; Wei-Ping Zhang; Er-Qing Wei (Neuroscience Bulletin, 2012)

Lymphatic microvessel density and vascular endothelial growth factor-C and -D as prognostic factors in breast cancer: a systematic review and meta-analysis of the literature - Jun Wang; Yan Guo; Baocheng Wang; Jingwang Bi; Kainan Li; Xiuju Liang; Huili Chu; Huihui Jiang (Molecular Biology Reports, 2012)

Formation of Volatile Halogenated By-Products During the Chlorination of Oxytetracycline - Bin Xu; He-Zhen Zhu; Yi-Li Lin; Kai-Yuan Shen; Wen-Hai Chu; Chen-Yan Hu; Kang-Ning Tian; Seleli Andrew Mwakagenda; Xiang-Yu Bi (Water, Air, & Soil Pollution, 2012)

A new plastic surgical technique for adult congenital webbed penis - Yue-bing Chen; Xian-fan Ding; Chong Luo; Shi-cheng Yu; Yan-lan YU; Bi-de Chen; Zhi-gen Zhang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2012)

Effects of indole-3-acetic acid and auxin transport inhibitors on the style curvature of three Alpinia species (Zingiberaceae) - Yin-Ling Luo; Ting-Ju Bi; Dong Li; Zhi-Long Su; Chuan Tao; Yan-Jiang Luo; Qing-Jun Li (Acta Physiologiae Plantarum, 2012)

Mantle-derived noble gases in ore-forming fluids of the granite-related Yaogangxian tungsten deposit, Southeastern China - Rui-Zhong Hu; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Jian-Tang Peng; You-Qiang Qi; Li-Yan Wu; Wen-Feng Wei (Mineralium Deposita, 2012)

Phylogenetic analysis of hemagglutinin genes of 40 H9N2 subtype avian influenza viruses isolated from poultry in China from 2010 to 2011 - Feng Chen; Zhuan-Qiang Yan; Jun Liu; Jun Ji; Shuang Chang; Di Liu; Jian-Ping Qin; Jing-Yun Ma; Ying-Zuo Bi; Qing-Mei Xie (Virus Genes, 2012)

Effect of riboflavin on postharvest disease of Asia pear and the possible mechanisms involved - Yongcai Li; Yan Yin; Yang Bi; Di Wang (Phytoparasitica, 2012)

Salicylic acid-altering Arabidopsis mutants response to salt stress - Lin Hao; Yan Zhao; Dandan Jin; Ling Zhang; Xiaohua Bi; Hongxing Chen; Qiang Xu; Chunyan Ma; Guangzhe Li (Plant and Soil, 2012)

The Group III Two-Component Histidine Kinase AlHK1 is Involved in Fungicides Resistance, Osmosensitivity, Spore Production and Impacts Negatively Pathogenicity in Alternaria longipes - Yi Yong Luo; Jin Kui Yang; Ming Liang Zhu; Chen Jian Liu; Hai Yan Li; Ze Bao Lu; Wen Zheng Pan; Zhong Hua Zhang; Wei Bi; Ke Qin Zhang (Current Microbiology, 2012)

Allelic variation and distribution of HMW glutenin subunit 1Ay in Triticum species - Xi-Gui Hu; Bi-Hua Wu; Zhe-Guang Bi; Deng-Cai Liu; Lian-Quan Zhang; Ze-Hong Yan; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2012)

Continuous and Noninvasive Measurement of Systolic and Diastolic Blood Pressure by One Mathematical Model with the Same Model Parameters and Two Separate Pulse Wave Velocities - Yan Chen; Changyun Wen; Guocai Tao; Min Bi (Annals of Biomedical Engineering, 2012)

Muscle injury induced by different types of contractions in dystrophic mdx mice - Jianwei Lou; Wenbo Bi; Wei Li; Yuying Zhao; Shuping Liu; Jinfan Zheng; Chuanzhu Yan (Journal of Muscle Research and Cell Motility, 2012)

Regioselectivity-reversal in acylation of 6-azauridine catalyzed by Burkholderia cepacia lipase - Zhao-Yu Wang; Yan-Hong Bi; Min-Hua Zong (Biotechnology Letters, 2012)

Clinical outcomes of fertility-sparing treatments in young patients with epithelial ovarian carcinoma - Jun Hu; Li-rong Zhu; Zhi-qing Liang; Yuan-guang Meng; Hong-yan Guo; Peng-peng Qu; Cai-ling Ma; Cong-jian Xu; Bi-bo Yuan (Journal of Zhejiang University-SCIENCE B, 2011)

Dissipation and Residue of Thiacloprid in Cabbage and Soil - Chen Wang; Wen-bi Guan; Hong-yan Zhang (Bulletin of Environmental Contamination and Toxicology, 2011)

Application of seismic anisotropy fluid detection technology in the Ken 71 well block of Shengli Oilfield - Li-Fei Bi; Zhong-Ping Qian; Feng Zhang; Xiao-Yan Chen; Shi-Chun Han; Mark Chapman (Applied Geophysics, 2011)

H2S Protects Hippocampal Neurons from Anoxia–Reoxygenation Through cAMP-Mediated PI3K/Akt/p70S6K Cell-Survival Signaling Pathways - Jian-Lin Shao; Xiao-Hong Wan; Yan Chen; Chun Bi; Hong-Mei Chen; Ying Zhong; Xin-Hua Heng; Jin-Qiao Qian (Journal of Molecular Neuroscience, 2011)

Phenotypic and molecular characterization of Photobacterium damselae , a pathogen of the cultured tongue sole Cynoglossus semilaevis in China - X‐J Zhang; G‐M Qin; X‐W Bing; B‐L Yan; K‐R Bi (New Zealand Journal of Marine and Freshwater Research, 2011)
Significant numbers of half‐smooth tongue sole ( Cynoglossus semilaevis ) raised on a marine fish farm in the P.R. China presented erratic swimming, loss of appetite and increased ventilation rate. Internally, diseased fish exhibited redness of liver, stomach and intestines, and white materials may be observed in the intestine. Mortality rates reached levels of up to 10% of the total fish on the farm per day. The dominant bacterial colonies were isolated from the liver, kidney and spleen of affected fish, and high pathogenicity of the isolates to Cynoglossus semilaevis , Paralichthys olivaceus and Synechogobius hasta was confirmed. The phenotypic characteristics of the isolates were studied extensively, including morphological, physiological and biochemical characteristics. The 16S rRNA and gyr B genes of a representative strain (ST1) were sequenced, and phylogenetic trees representing genetic relatedness between the isolate and publicly available 16S rRNA and gyr B gene sequence from the GenBank database was constructed as an aid to identification. The sequenced 16S rRNA gene (GenBank accession No. GU228793) and the gyr B gene of strain ST1 (GenBank accession No. GU228794) exhibited high similarity (98–99%) to those of Photobacterium damselae from the GenBank database. In addition, the activities of extracellular enzymes and haemolysin were also studied, the results showed that the isolates produced beta‐haemolysis on rabbit blood agar, lecithinase, proteinase and DNase but diastase, lipase and gelatinase were not produced. Antibiotic susceptibility tests showed that the isolates exhibited around 80% of susceptibility to 36 various antibiotics tested.

He and Ar isotopic compositions and genetic implications for the giant Shizhuyuan W–Sn–Bi–Mo deposit, Hunan Province, South China - Li-Yan Wu; Rui-Zhong Hu; Jian-Tang Peng; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Qiao-Yun Wang; Ya-Ying Liu (International Geology Review, 2011)

Dendritic cell co-transfected with FasL and allergen genes induces T cell tolerance and decreases airway inflammation in allergen induced murine model - Yan Wang; Yutian Bi; Kui Wu; Changzheng Wang (Molecular Biology Reports, 2011)

High glucose condition upregulated Txnip expression level in rat mesangial cells through ROS/MEK/MAPK pathway - Shaohong Fang; Yuhong Jin; Haixia Zheng; Junxia Yan; Yunxia Cui; Huimei Bi; Huijie Jia; Huishu Zhang; Yi Wang; Liying Na; Xu Gao; Hongbo Zhou (Molecular and Cellular Biochemistry, 2011)

Proteomic analysis of cell lines to identify the irinotecan resistance proteins - Xing-Chen Peng; Feng-Ming Gong; Meng Wei; Xi Chen; Ye Chen; Ke Cheng; Feng Gao; Feng Xu; Feng Bi; Ji-Yan Liu (Journal of Biosciences, 2010)

Synthesis, structure characterization, and biological evaluation of some new 1,2,3-benzotriazole derivatives - Jun Wan; Xia Yan; Cuiping Ma; Sai Bi; Hai-Liang Zhu (Medicinal Chemistry Research, 2010)

A study of perfectly matched layers for joint multicomponent reverse-time migration - Qi-Zhen Du; Rui-Yan Sun; Tong Qin; Yi-Tong Zhu; Li-Fei Bi (Applied Geophysics, 2010)

Expression and characterization of two domains of Pinellia ternata agglutinin (PTA), a plant agglutinin from Pinellia ternata with antifungal activity - Li-Jun Ling; Yan-Zhuo Yang; Yu-Rong Bi (World Journal of Microbiology and Biotechnology, 2010)

Continuous and Noninvasive Blood Pressure Measurement: A Novel Modeling Methodology of the Relationship Between Blood Pressure and Pulse Wave Velocity - Yan Chen; Changyun Wen; Guocai Tao; Min Bi; Guoqi Li (Annals of Biomedical Engineering, 2009)

Eleven novel microsatellite markers developed from the living fossil Ginkgo biloba (Ginkgoaceae) - Xiao-Ling Yan; Ye-Ye Chen; Bi-Cai Guan; Cheng-Xin Fu (Conservation Genetics, 2009)

Increased expression of Toll-like receptors 4 and 9 in human lung cancer - Yan-Bei Zhang; Feng-Lian He; Ming Fang; Tian-Feng Hua; Bi-Dan Hu; Zhi-Hong Zhang; Qi Cao; Rong-Yu Liu (Molecular Biology Reports, 2009)

Crystallisation conditions (T, P, fO2) from mineral chemistry of Cu- and Au-mineralised alkaline intrusions in the Red River–Jinshajiang alkaline igneous belt, western Yunnan Province, China - Bi Xianwu; Hu Ruizhong; J. J. Hanley; J. E. Mungall; Peng Jiantang; Shang Linbo; Wu Kaixing; Suang Yan; Li Hongli; Hu Xiaoyan (Mineralogy and Petrology, 2009)

Consumption of Grape Seed Extract Prevents Amyloid-β Deposition and Attenuates Inflammation in Brain of an Alzheimer’s Disease Mouse - Yan-Jiang Wang; Philip Thomas; Jin-Hua Zhong; Fang-Fang Bi; Shantha Kosaraju; Anthony Pollard; Michael Fenech; Xin-Fu Zhou (Neurotoxicity Research, 2009)

Induction of diploid gynogenesis in turbot Scophthalmus maximus with left-eyed flounder Paralichthys olivaceus sperm - Jian-He Xu; Feng You; Wei Sun; Bin-Lun Yan; Pei-Jun Zhang; Bi-Xiang Jing (Aquaculture International, 2008)

Molecular mechanism underlying differential apoptosis between human melanoma cell lines UACC903 and UACC903(+6) revealed by mitochondria-focused cDNA microarrays - Qiuyang Zhang; Jun Wu; AnhThu Nguyen; Bi-Dar Wang; Ping He; Georges St. Laurent; Owen M. Rennert; Yan A. Su (Apoptosis, 2008)

RhoC is essential for the metastasis of gastric cancer - Na Liu; Guoyun Zhang; Feng Bi; Yanglin Pan; Yan Xue; Yongquan Shi; Liping Yao; Lina Zhao; Yi Zheng; Daiming Fan (Journal of Molecular Medicine, 2007)

Hydrogen peroxide-induced chlorophyll a bleaching in the cytochrome b 6 f complex: a simple and effective assay for stability of the complex in detergent solutions - Xiao-Bo Chen; Xiao-Hui Zhao; Yi Zhu; Yan-Dao Gong; Liang-Bi Li; Jian-Ping Zhang; Ting-Yun Kuang (Photosynthesis Research, 2007)

Production and analysis of transgenic wheat (Triticum aestivum L.) with improved insect resistance by the introduction of cowpea trypsin inhibitor gene - Rui-Ming Bi; Hai-Yan Jia; De-Shun Feng; Hong-Gang Wang (Euphytica, 2006)

Synthesis, characterization and antibacterial activity of new Ln(III) complexes with an unsymmetrical schiff base ligand - BI Caifeng; Yan Liangliang; Fan Yuhua; Zhang Xia; Wang Aidong (Journal of Ocean University of China, 2006)

Construction of a genetic linkage map and QTL analysis of fiber-related traits in upland cotton (Gossypium hirsutum L.) - Zheng-Sheng Zhang; Yue-Hua Xiao; Ming Luo; Xian-Bi Li; Xiao-Ying Luo; Lei Hou; De-Mou Li; Yan Pei (Euphytica, 2005)

Effect of erythromycin on metabolism of quetiapine in Chinese suffering from schizophrenia - Kun-Yan Li; Xin Li; Ze-Neng Cheng; Bi-Kui Zhang; Wen-Xing Peng; Huan-De Li (European Journal of Clinical Pharmacology, 2005)

Production of Linolenic Acid by Mortierella isabellina Grown on Octadecanol - Mo Xian; Yijian Kang; Jicang Yan; Junhong Liu; Yingli Bi; Kaiji Zhen (Current Microbiology, 2002)